Adhesive sheet and optical laminate
By combining light diffusing particles and transparent adhesive layer in the adhesive layer and curing through active energy rays, the problems of segment difference follow-up and light diffusing uniformity are solved, and efficient light diffusing and brightness uniformity are achieved. It is an optical laminated body such as a liquid crystal display.
Patent Information
- Application Number
- CN202010876312.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2019-09-05
- Filing Date
- 2020-08-25
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2040-08-25
AI Technical Summary
In the prior art, while improving the light diffusion performance, the light diffusion adhesive layer is prone to decrease the segment difference following and the light diffusion uniformity, and high adhesion and energy storage modulus will affect the performance of the adhesive.
The composite adhesive layer is adopted, combining the light-diffusing adhesive layer containing light-diffusing particles and the transparent adhesive layer without light-diffusing particles, and curing it by active energy rays to ensure the low elastic modulus of the transparent adhesive layer. and high adhesion force to achieve optimization of segment difference follow-up and light diffusion uniformity.
It has achieved an adhesive sheet and optical laminate with excellent light diffusivity, excellent segment difference follow-up ability and good brightness uneven suppression. It can maintain performance under high temperature and high humidity conditions, avoid bubbles or floats, and improve product stability and ability Vision.
Smart Images

Figure CN112442325B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a light-diffusing adhesive sheet and an optical layered body obtained by using the adhesive sheet. Background Art
[0002] In recent years, various mobile electronic devices such as smartphones and tablet terminals have displays using display modules that have liquid crystal elements, light-emitting diodes (LED elements), organic electroluminescent (organic EL) elements, etc., and most of these displays are touch panels.
[0003] In the above-described display, an adhesive may be used to bond, for example, a display module to a protection panel that protects the display module, or a display module to a backlight system that illuminates the display module.
[0004] Here, when the protective panel and the display module are bonded together using an adhesive, a frame-shaped printed layer may exist in the form of a step on the display module side of the protective panel. At this time, if the adhesive layer does not follow the step, the adhesive layer will float near the step, thereby causing light reflection loss. Therefore, the adhesive layer is required to follow the step. In addition, the step followability is sometimes also required for other parts of the display.
[0005] In order to solve the above technical problems, Patent Document 1 discloses a method for preparing a 3D printed circuit board having a shear storage modulus (G') of 1.0 × 10 5 Pa or less and a gel fraction of 40% or more. The adhesive layer reduces the storage elastic modulus at room temperature, thereby improving the step followability.
[0006] Prior art literature
[0007] Patent Literature
[0008] Patent Document 1: Japanese Patent Application Publication No. 2010-97070 Summary of the invention
[0009] Technical Problems to be Solved by the Invention
[0010] On the other hand, in a display using a backlight system, a problem of uneven brightness (uneven brightness) may occur due to the light source of the backlight. In order to solve this problem, a light diffusion plate is provided.
[0011] Here, from the constituent element of reducing display, seek the angle of thinning or low cost or strengthen the angle of light diffusion performance, consider to use the adhesive layer with light diffusion in the mode of replacing with above-mentioned light diffusion plate or in the mode of using simultaneously with above-mentioned light diffusion plate.This light diffusion adhesive layer can be obtained by adding light diffusion particles in adhesive layer, improving haze value.But the haze value of such light diffusion adhesive layer is higher, then storage modulus becomes higher, and adhesive force reduces simultaneously.Therefore, the problem that step difference follow-up property reduces may occur in this light diffusion adhesive layer.In addition, the problem that the homogeneity of light diffusion reduces because of step difference may also occur sometimes.
[0012] The present invention has been made in view of the above-mentioned actual situation, and an object of the present invention is to provide an adhesive sheet and an optical laminate having excellent uniformity of light diffusion and excellent step followability.
[0013] Technical means to solve technical problems
[0014] In order to achieve the above-mentioned purpose, first, the present invention provides an adhesive sheet, characterized in that it has a composite adhesive layer, the composite adhesive layer has a light-diffusing adhesive layer containing light-diffusing particles and a transparent adhesive layer not containing light-diffusing particles, and at least one of the light-diffusing adhesive layer and the transparent adhesive layer is composed of an active energy ray-curable adhesive (Invention 1).
[0015] The adhesive sheet of the above invention (Invention 1) can make a transparent adhesive layer that does not contain light-diffusing particles contact with an adherend having a step difference and adhere to the adherend. As a result, the light-diffusing adhesive layer can be suppressed from being compressed or deformed due to the step difference of the adherend, and the uniformity of light diffusion of the light-diffusing adhesive layer and the composite adhesive layer can be maintained. In addition, since the elastic modulus of the transparent adhesive layer is lower than that of the light-diffusing adhesive layer, it can maintain flexibility. Therefore, by making the transparent adhesive layer contact with an adherend having a step difference and adhere to the adherend, the composite adhesive layer can easily follow the step difference of the adherend. Therefore, the initial step difference followability is excellent, and after active energy ray curing, the step difference followability is excellent under high temperature and high humidity conditions.
[0016] In the above invention (Invention 1), it is preferred that the haze value of the composite pressure-sensitive adhesive layer is 40% or more and 99% or less (Invention 2).
[0017] In the above inventions (Inventions 1 and 2), it is preferred that the storage elastic modulus G1 of the composite adhesive layer at 23° C. is 0.001 MPa or more and 0.2 MPa or less (Invention 3).
[0018] In the above inventions (Inventions 1 to 3), it is preferred that the storage elastic modulus G2 of the composite pressure-sensitive adhesive layer at 23° C. after irradiation with active energy rays is 0.08 MPa or more and 10 MPa or less (Invention 4).
[0019] In the above inventions (Inventions 1 to 4), it is preferred that the storage modulus change rate ΔG', which is the ratio of the storage modulus G2 of the composite adhesive layer at 23°C to the storage modulus G1 of the composite adhesive layer at 23°C after irradiation with active energy rays, is greater than 1.1 and less than 100 (Invention 5).
[0020] In the above inventions (Inventions 1 to 5), it is preferred that the adhesive strength of the transparent adhesive layer side of the adhesive sheet to the soda lime glass is 20 N / 25 mm or more and 80 N / 25 mm or less (Invention 6).
[0021] In the above inventions (Inventions 1 to 6), it is preferred that the adhesive strength of the transparent adhesive layer in the adhesive sheet to soda lime glass after irradiation with active energy rays is 20 N / 25 mm or more and 80 N / 25 mm or less (Invention 7).
[0022] In the above inventions (Inventions 1 to 7), it is preferred that the adhesive strength of the light diffusing adhesive layer side of the adhesive sheet to the soda lime glass is 1 N / 25 mm or more and 60 N / 25 mm or less (Invention 8).
[0023] In the above inventions (Inventions 1 to 8), it is preferred that the light diffusing adhesive layer side of the adhesive sheet has an adhesive strength to soda lime glass of 10 N / 25 mm or more and 60 N / 25 mm or less after irradiation with active energy rays (Invention 9).
[0024] In the above inventions (Inventions 1 to 9), it is preferred that the thickness of the composite adhesive layer is 20 μm or more and 1000 μm or less (Invention 10).
[0025] In the above inventions (Inventions 1 to 10), it is preferred that the thickness of the light diffusing adhesive layer is 10 μm or more and 500 μm or less (Invention 11).
[0026] In the above inventions (Inventions 1 to 11), it is preferred that the transparent adhesive layer has a thickness of 10 μm or more and 500 μm or less (Invention 12).
[0027] In the above inventions (Inventions 1 to 12), preferably, the adhesive sheet includes two release sheets, and the composite adhesive layer is sandwiched by the release sheets so as to be in contact with release surfaces of the two release sheets (Invention 13).
[0028] Second, the present invention provides an optical layer stack, which comprises an optical component, another optical component and a cured composite adhesive layer that bonds the one optical component and the other optical component to each other, characterized in that the cured composite adhesive layer is a layer formed by curing the composite adhesive layer of the adhesive sheet (Inventions 1 to 13) with active energy rays (Invention 14).
[0029] In the above invention (Invention 14), it is preferred that at least one of the one optical component and the other optical component has projections and depressions on the surface of the side bonded by the cured composite adhesive layer, and the transparent adhesive layer of the cured composite adhesive layer is in contact with the projections and depressions (Invention 15).
[0030] Effects of the Invention
[0031] The adhesive sheet of the present invention has sufficiently uniform light diffusion and excellent step-adjustability. In addition, the optical layered body of the present invention has excellent step-adjustability and brightness unevenness suppression. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 This is a cross-sectional view of an adhesive sheet according to one embodiment of the present invention.
[0033] Figure 2 This is a cross-sectional view of an optical layered body according to one embodiment of the present invention.
[0034] Figure 3 This is a cross-sectional view of an optical layered body according to another embodiment of the present invention.
[0035] Figure 4 This is a cross-sectional view of an adhesive sheet according to another embodiment of the present invention.
[0036] Description of Reference Numerals
[0037] 1, 1A: adhesive sheet; 11: composite adhesive layer; 111: light diffusion adhesive layer; 112: transparent adhesive layer; 12a, 12b: release sheet; 2A, 2B: optical laminate; 11': cured composite adhesive layer; 21: first optical component; 22: second optical component; 23: printed layer; 30: backlight source; 31: substrate; 32: light emitter; 40: display unit. DETAILED DESCRIPTION
[0038] Hereinafter, embodiments of the present invention will be described.
[0039] [Adhesive sheet]
[0040] An adhesive sheet according to one embodiment of the present invention has a composite adhesive layer, wherein the composite adhesive layer includes a light-diffusing adhesive layer containing light-diffusing particles and a transparent adhesive layer not containing light-diffusing particles. Furthermore, at least one of the light-diffusing adhesive layer and the transparent adhesive layer is composed of an active energy ray-curable adhesive. In addition, the "active energy ray-curable adhesive" in this specification refers to an adhesive that is cured by irradiation with active energy rays. Therefore, the "active energy ray-curable adhesive" does not include an adhesive that has been cured by previous irradiation with active energy rays to the extent that it cannot be further cured.
[0041] In the above-mentioned composite adhesive layer, the transparent adhesive layer may be present in two or more layers. In this case, it is preferred that at least one layer of the transparent adhesive layer is located on the surface in contact with the adherend, especially the adherend with a step difference (convex and concave). In addition, the light-diffusing adhesive layer may be present in two or more layers, but at least one of the outermost layers of the composite adhesive layer is a transparent adhesive layer. In addition, from the perspective of controlling the haze value of the composite adhesive layer, it is preferred that the light-diffusing adhesive layer is one layer.
[0042] When the light-diffusing adhesive layer containing light-diffusing particles is contacted and follows the step (concave-convex) of the adherend, the light-diffusing adhesive layer can be compressed or deformed due to the step of the adherend. Thus, the density of the light-diffusing particles of the light-diffusing adhesive layer can be caused to become uneven, and the uniformity of light diffusion is impaired. The adhesive sheet of the present embodiment can make the transparent adhesive layer not containing light-diffusing particles contact and be attached to the adherend with the step. Thus, the light-diffusing adhesive layer can be suppressed from being compressed or deformed due to the step of the adherend, and the uniformity of light diffusion of the light-diffusing adhesive layer and the composite adhesive layer can be maintained. According to the composite adhesive layer (composite adhesive layer after curing) with uniform light diffusion, an optical laminate (display body) with excellent brightness unevenness suppression can be obtained.
[0043] In addition, since the light-diffusing adhesive layer containing light-diffusing particles is easy to have a high elastic modulus and has a tendency to become less flexible, the followability of the adherend with a step difference (concave-convex) is easily reduced. The adhesive sheet of this embodiment enables the transparent adhesive layer that does not contain light-diffusing particles to contact and attach to the adherend with a step difference. Thus, the composite adhesive layer is easy to follow the step difference, and bubbles or floating near the step difference can be suppressed. In addition, after the component (such as a glass plate) with the step difference is bonded to another component (such as a glass plate) using the above-mentioned composite adhesive layer, the composite adhesive layer is cured by active energy ray irradiation to form a cured composite adhesive layer. In this way, a laminated body formed by bonding two components using the cured composite adhesive layer can be obtained. Even if the laminated body is placed under high temperature and high humidity conditions, such as 85°C and 85%RH for 72 hours, bubbles or floating, peeling, etc. can be suppressed near the step difference. That is, the adhesive sheet of the present embodiment is excellent in initial step followability and step followability under high temperature and high humidity conditions.
[0044] Further, because the adhesion of the light-diffusing adhesive layer containing light-diffusing particles is easily reduced, therefore, when it is attached to a component (such as a plastic plate) that degassing occurs at high temperatures or changes over time, bubbles or frothing, peeling and other foaming occur easily. The adhesive sheet of the present embodiment can make the transparent adhesive layer that has high adhesion and does not contain light-diffusing particles contact and attach to the component that degassing occurs. In the adhesive sheet of the present embodiment, it is preferred that any layer in the transparent adhesive layer and the light-diffusing adhesive layer is composed of an adhesive of active energy ray curing property, and further, it is more preferred that the entire composite adhesive layer is made of active energy ray curing property. At this time, after the composite adhesive layer is attached to the adherend, the composite adhesive layer is cured by active energy ray irradiation to make the composite adhesive layer after curing, so that the anti-foaming property of the composite adhesive layer after curing becomes excellent. For example, after a component (such as a plastic plate) that is subject to degassing is bonded to another component (such as a glass plate) using the above-mentioned composite adhesive layer, the composite adhesive layer is cured by irradiation with active energy rays to form a cured composite adhesive layer. In this way, a laminated body formed by bonding two components using a cured composite adhesive layer can be obtained. Even if the laminated body is placed under high temperature and high humidity conditions, such as 85°C and 85% RH for 72 hours, bubbles, floating, peeling, and other bubbles can be suppressed at the interface between the cured composite adhesive layer and the adherend (especially the plastic plate).
[0045] Here, when a solvent-based material is used to form a thick film adhesive layer, a plurality of adhesive layers are usually stacked to form the thick film adhesive layer. When a plurality of light-diffusing adhesive layers are stacked to obtain an adhesive layer with a desired haze value, especially an adhesive layer with a high haze value, if the haze value of each light-diffusing adhesive layer deviates from the target haze value, then when a plurality of light-diffusing adhesive layers are stacked, the deviation from the target haze value increases, and it becomes impossible to obtain an adhesive layer with the desired haze value. Therefore, there is a problem that the manufacturing yield is easily reduced. In contrast, by using a light-diffusing adhesive layer and a transparent adhesive layer as in the adhesive sheet of the present embodiment, the cumulative thickness of the transparent adhesive layer can be utilized while reducing the number of layers of the light-diffusing adhesive layer (preferably made into one layer). Thus, it is easy to obtain an adhesive layer (composite adhesive layer) that stably has a desired haze value, which can improve product stability.
[0046] The haze value (measured in accordance with JIS K7136:2000) of the composite adhesive layer in the adhesive sheet of the present embodiment is preferably 40% or more, more preferably 50% or more, particularly preferably 60% or more, and further preferably 80% or more. Thus, it is easy to obtain good light diffusion and good brightness unevenness prevention. On the other hand, from the perspective of visibility of the optical laminate (display body), the haze value of the composite adhesive layer is preferably 99% or less, more preferably 98% or less, particularly preferably 97% or less, and further preferably 96% or less. In addition, the haze value of the composite adhesive layer does not change almost at all before and after irradiation with active energy rays.
[0047] The lower limit of the total light transmittance of the composite adhesive layer in the adhesive sheet of the present embodiment (the value measured in accordance with JIS K7361-1:1997) is preferably 70% or more, particularly preferably 90% or more, and further preferably 99% or more. By making the total light transmittance of the composite adhesive layer as described above, the visibility as an optical laminate (display body) becomes good. On the other hand, the upper limit of the total light transmittance of the composite adhesive layer is not particularly limited, but is usually 100% or less. In addition, the total light transmittance of the composite adhesive layer does not change much before and after irradiation with active energy rays.
[0048] From the perspective of step-following performance under high-temperature and high-humidity conditions, the storage modulus G1 of the composite adhesive layer of the adhesive sheet according to this embodiment at 23°C is preferably 0.001 MPa or more, more preferably 0.01 MPa or more, particularly preferably 0.02 MPa or more, and further preferably 0.04 MPa or more. In addition, the above storage modulus G1 is preferably 0.2 MPa or less, more preferably 0.1 MPa or less, particularly preferably 0.09 MPa or less, and further preferably 0.08 MPa or less. Thereby, the initial step-following performance becomes more excellent. In addition, the storage modulus in this specification is a value measured by the torsional shear method in accordance with JIS K7244-6 at a measurement frequency of 1 Hz. Specifically, as shown in the test examples described later.
[0049] The storage modulus G2 of the composite adhesive layer of the adhesive sheet according to this embodiment at 23°C after irradiation with active energy rays is preferably 0.08 MPa or more, more preferably 0.09 MPa or more, particularly preferably 0.10 MPa or more, and further preferably 0.11 MPa or more. Thereby, the step-following performance under high-temperature and high-humidity conditions becomes more excellent. In addition, the above storage modulus G2 is preferably 10 MPa or less, more preferably 5 MPa or less, particularly preferably 1 MPa or less, and further preferably 0.2 MPa or less. Thereby, good adhesiveness is exhibited, and the adhesiveness to the adherend becomes more excellent. In addition, "after irradiation with active energy rays" means after irradiation with active energy rays at an irradiation dose equivalent to the irradiation dose of the active energy ray-curable adhesive layer (composite adhesive layer) when assembled into a product. In this specification, the irradiation dose of the active energy rays shown in Test Example 1 is used as a reference, but it is not limited thereto.
[0050] The storage modulus change rate ΔG', which is the ratio of the above storage modulus G2 to the above storage modulus G1 (storage modulus G2 / storage modulus G1), is preferably 1.1 or more, more preferably 1.2 or more, particularly preferably 1.4 or more, and further preferably 1.8 or more. In addition, the above storage modulus change rate ΔG' is preferably 100 or less, more preferably 10 or less, particularly preferably 5 or less, and further preferably 2.5 or less. By making the storage modulus change rate ΔG' within the above range, the initial step-following performance and the step-following performance under high-temperature and high-humidity conditions can be made more excellent.
[0051] From the perspective of stably maintaining the light-diffusing particles in the light-diffusing adhesive layer, the storage modulus GD1 of the light-diffusing adhesive layer of the present embodiment at 23°C is preferably 0.001MPa or more, more preferably 0.01MPa or more, particularly preferably 0.02MPa or more, and further preferably 0.04MPa or more. In addition, the above-mentioned storage modulus GD1 is preferably 0.2MPa or less, more preferably 0.16MPa or less, particularly preferably 0.12MPa or less, and further preferably 0.09MPa or less. Thus, it is possible to ensure good adhesion with the transparent adhesive layer.
[0052] When the light diffusion adhesive layer is composed of an active energy ray curable adhesive, from the perspective of anti-foaming, the light diffusion adhesive layer is preferably 0.08MPa or more, more preferably 0.10MPa or more, particularly preferably 0.12MPa or more, and further preferably 0.15MPa or more after irradiating the active energy ray. In addition, the above-mentioned storage modulus GD2 is preferably 10MPa or less, more preferably 5MPa or less, particularly preferably 1MPa or less, and further preferably 0.3MPa or less. Thus, good adhesion is shown, and the adhesion to the adherend becomes more excellent.
[0053] The storage modulus change rate ΔGD, which is the ratio of the storage modulus GD2 to the storage modulus GD1 (storage modulus GD2 / storage modulus GD1), is preferably 1.1 or more, more preferably 1.4 or more, particularly preferably 1.8 or more, and further preferably 2.1 or more. In addition, the storage modulus change rate ΔGD is preferably 100 or less, more preferably 10 or less, particularly preferably 5 or less, and further preferably 3 or less. By making the storage modulus change rate ΔGD within the above range, it is possible to achieve a good balance between the maintenance of adhesive force after curing and anti-foaming properties.
[0054] From the perspective of step followability under high temperature and high humidity conditions, the storage modulus GT1 of the transparent adhesive layer of this embodiment at 23°C is preferably 0.001MPa or more, more preferably 0.01MPa or more, particularly preferably 0.02MPa or more, and further preferably 0.04MPa or more. In addition, the above storage modulus GT1 is preferably 0.2MPa or less, more preferably 0.1MPa or less, particularly preferably 0.09MPa or less, and further preferably 0.08MPa or less. Thus, the initial step followability becomes more excellent.
[0055] When the transparent adhesive layer is composed of an active energy ray-curable adhesive, the storage modulus GT2 of the transparent adhesive layer at 23°C after irradiation with active energy rays is preferably 0.08MPa or more, more preferably 0.09MPa or more, particularly preferably 0.10MPa or more, and further preferably 0.11MPa or more. Thus, the step tracking property under high temperature and high humidity conditions becomes more excellent. In addition, the above-mentioned storage modulus GT2 is preferably 10MPa or less, more preferably 5MPa or less, particularly preferably 1MPa or less, and further preferably 0.2MPa or less. Thus, good adhesion is shown, and the adhesion to the adherend becomes more excellent.
[0056] The storage modulus change rate ΔGT, which is the ratio of the storage modulus GT2 to the storage modulus GT1 (storage modulus GT2 / storage modulus GT1), is preferably 1.1 or more, more preferably 1.2 or more, particularly preferably 1.6 or more, and further preferably 1.8 or more. In addition, the storage modulus change rate ΔGT is preferably 100 or less, more preferably 10 or less, particularly preferably 5 or less, further preferably 3 or less, and further preferably 2.5 or less. By making the storage modulus change rate ΔGT within the above range, the initial step followability and the step followability under high temperature and high humidity conditions can be made more excellent.
[0057] From the perspective of step tracking under high temperature and high humidity conditions, the gel fraction of the composite adhesive layer of the adhesive sheet of this embodiment is preferably 20% or more, more preferably 30% or more, particularly preferably 40% or more, and further preferably 50% or more. In addition, the above-mentioned gel fraction is preferably 80% or less, more preferably 70% or less, particularly preferably 65% or less, and further preferably 60% or less. As a result, the initial step tracking becomes more excellent. In addition, the method for determining the gel fraction of the adhesive in this specification is shown in the test example described later.
[0058] The composite adhesive layer of the adhesive sheet of the present embodiment preferably has a gel fraction of 40% or more after irradiation with active energy rays, more preferably 50% or more, particularly preferably 60% or more, and further preferably 65% or more. As a result, the step tracking property under high temperature and high humidity conditions becomes even better. In addition, the gel fraction is preferably 99% or less, more preferably 89% or less, particularly preferably 80% or less, and further preferably 75% or less. As a result, good adhesion is exhibited, and the adhesion to the adherend becomes even better.
[0059] From the perspective of maintaining the dispersed state of the light-diffusing particles and effectively exerting the uneven brightness suppression, the gel fraction of the light-diffusing adhesive layer of the present embodiment is preferably 30% or more, more preferably 40% or more, particularly preferably 50% or more, and further preferably 55% or more. In addition, the gel fraction is preferably 90% or less, more preferably 80% or less, particularly preferably 70% or less, and further preferably 65% or less. Thus, good adhesion with the transparent adhesive layer can be ensured.
[0060] When the light-diffusing adhesive layer is composed of an active energy ray-curable adhesive, from the perspective of anti-foaming, the gel fraction of the light-diffusing adhesive layer after irradiation with active energy rays is preferably 40% or more, more preferably 50% or more, particularly preferably 60% or more, and further preferably 65% or more. In addition, the gel fraction is preferably 99% or less, more preferably 90% or less, particularly preferably 85% or less, and further preferably 80% or less. Thus, good adhesion is exhibited, and the adhesion to the adherend becomes more excellent.
[0061] From the perspective of step followability under high temperature and high humidity conditions, the gel fraction of the transparent adhesive layer of this embodiment is preferably 20% or more, more preferably 30% or more, particularly preferably 40% or more, and further preferably 50% or more. In addition, the gel fraction is preferably 80% or less, more preferably 70% or less, particularly preferably 60% or less, and further preferably 55% or less. Thus, the initial step followability becomes even better.
[0062] When the transparent adhesive layer is composed of an active energy ray-curable adhesive, the gel fraction of the transparent adhesive layer after irradiation with active energy rays is preferably 40% or more, more preferably 50% or more, particularly preferably 60% or more, and further preferably 65% or more. Thus, the step tracking property under high temperature and high humidity conditions becomes even better. In addition, the gel fraction is preferably 98% or less, more preferably 87% or less, particularly preferably 75% or less, and further preferably 70% or less. Thus, good adhesion is exhibited, and the adhesion to the adherend becomes even better.
[0063] From the perspective of step tracking and handling under high temperature and high humidity conditions, the adhesive force of the transparent adhesive layer side of the adhesive sheet of this embodiment to the soda-lime glass is preferably 20N / 25mm or more, more preferably 30N / 25mm or more, particularly preferably 35N / 25mm or more, and further preferably 40N / 25mm or more. In addition, the above-mentioned adhesive force is preferably 80N / 25mm or less, more preferably 70N / 25mm or less, particularly preferably 60N / 25mm or less, and further preferably 50N / 25mm or less. Thus, good reoperability can be obtained, and the adherend can be reused even if a bonding error occurs.
[0064] The transparent adhesive layer side of the adhesive sheet of the present embodiment is preferably 20N / 25mm or more, more preferably 30N / 25mm or more, particularly preferably 40N / 25mm or more, and further preferably 45N / 25mm or more after irradiating the active energy ray. Thus, the step tracking property under high temperature and high humidity conditions becomes more excellent. In addition, the above-mentioned adhesion is preferably 80N / 25mm or less, more preferably 70N / 25mm or less, particularly preferably 60N / 25mm or less, and further preferably 50N / 25mm or less. Thus, good reoperability can be obtained.
[0065] From the perspective of handling, the light diffusion adhesive layer side of the adhesive sheet of the present embodiment preferably has an adhesive force of 1N / 25mm or more, more preferably 4N / 25mm or more, particularly preferably 8N / 25mm or more, and further preferably 13N / 25mm or more. In addition, the above-mentioned adhesive force is preferably 60N / 25mm or less, more preferably 50N / 25mm or less, particularly preferably 40N / 25mm or less, and further preferably 35N / 25mm or less. Thus, good reoperability can be obtained, and the adherend can be reused even if a bonding error occurs.
[0066] The light diffusion adhesive layer side of the adhesive sheet of the present embodiment is preferably 10N / 25mm or more, more preferably 15N / 25mm or more, particularly preferably 20N / 25mm or more, and further preferably 25N / 25mm or more, after irradiating the active energy ray, The adhesion to the soda-lime glass. Thus, the anti-foaming property becomes more excellent. In addition, the above-mentioned adhesion is preferably 60N / 25mm or less, more preferably 50N / 25mm or less, particularly preferably 45N / 25mm or less, and further preferably 40N / 25mm or less. Thus, good reoperability can be obtained.
[0067] Here, the adhesive strength in this specification refers to the adhesive strength measured by the 180-degree peeling method basically in accordance with JIS Z0237:2009, wherein a measurement sample is prepared into 25 mm wide and 100 mm long, and the measurement sample is attached to a to-be-adhered object, and after being pressurized at 0.5 MPa and 50° C. for 20 minutes, it is left under the conditions of normal pressure, 23° C., and 50% RH for 24 hours, and then measured at a peeling speed of 300 mm / min.
[0068] The thickness of the composite adhesive layer in the adhesive sheet of the present embodiment is preferably 20 μm or more, more preferably 40 μm or more, particularly preferably 60 μm or more, and further preferably 80 μm or more. Thus, the step difference (concave and convex) of the adherend can be well buried, and the step difference tracking property becomes more excellent. In addition, the thickness of the composite adhesive layer is preferably 1000 μm or less, more preferably 800 μm or less, particularly preferably 400 μm or less, and further preferably 200 μm or less. Thus, the processability becomes good, and in addition, it is not easy to produce a poor appearance caused by extrusion marks, etc.
[0069] The thickness of the light diffusion adhesive layer of the present embodiment is preferably more than 10 μm, more preferably more than 20 μm, particularly preferably more than 30 μm, and further preferably more than 40 μm. Thus, it is easy to obtain the desired light diffusion or haze value, and it is also easy to obtain the desired adhesion. In addition, the thickness of the light diffusion adhesive layer is preferably less than 500 μm, more preferably less than 400 μm, particularly preferably less than 200 μm, and further preferably less than 100 μm. Thus, it is easy to obtain the desired light diffusion or haze value, and the processability also becomes good.
[0070] In the adhesive sheet of this embodiment, the thickness of the transparent adhesive layer on the surface in contact with the step (convex and concave) of the adherend is preferably greater than the height of the step of the adherend. Thus, the transparent adhesive layer can be used to absorb the step of the adherend, and the light-diffusing adhesive layer can be more effectively prevented from being compressed or deformed due to the step. Therefore, the uniformity of light diffusion of the light-diffusing adhesive layer (composite adhesive layer) becomes higher.
[0071] Specifically, the thickness of the transparent adhesive layer of the present embodiment is preferably 10 μm or more, more preferably 20 μm or more, particularly preferably 30 μm or more, and further preferably 40 μm or more. As a result, the uniformity of light diffusion, the step tracking property under high temperature and high humidity conditions, and the anti-foaming property of the composite adhesive layer become more excellent. On the other hand, the thickness of the transparent adhesive layer is preferably 500 μm or less, more preferably 400 μm or less, particularly preferably 200 μm or less, and further preferably 100 μm or less. As a result, the processability becomes good, and it is not easy to produce poor appearance caused by extrusion marks, etc. In addition, as described later Figure 4 When there are a plurality of transparent adhesive layers as shown, the above thickness is the thickness of one transparent adhesive layer.
[0072] Preferably, the composite adhesive layer is an adhesive layer for bonding one optical component to another optical component. The optical component will be described later. In the optical laminate (display) obtained by using the composite adhesive layer of the adhesive sheet of the present embodiment, the optical diffusion of the composite adhesive layer is made uniform, thereby suppressing the uneven brightness of the optical laminate (display). However, the adhesive sheet of the present embodiment is not limited to the use in the optical laminate or display.
[0073] Figure 1 Detailed structure of an example of the adhesive sheet according to the present embodiment is shown in FIG.
[0074] like Figure 1 As shown, the adhesive sheet 1 is composed of two release sheets 12a, 12b and a composite adhesive layer 11, and the composite adhesive layer 11 is sandwiched by the two release sheets 12a, 12b in a manner of contacting the release surfaces of the two release sheets 12a, 12b. In addition, the release surface of the release sheet in this specification refers to the surface of the release sheet that has release properties, and also includes any one of the surfaces that have been subjected to release treatment and the surfaces that show release properties even if no release treatment is applied.
[0075] The composite adhesive layer 11 of this embodiment is a laminate of a light diffusing adhesive layer 111 and a transparent adhesive layer 112. However, the present invention is not limited thereto. The transparent adhesive layer 112 is preferably located on the surface of the composite adhesive layer 11 that contacts the step of the adherend.
[0076] 1. Each component
[0077] 1-1. Composite adhesive layer
[0078] Preferably, the light-diffusing adhesive layer 111 is composed of an adhesive containing light-diffusing particles. On the other hand, it is preferred that the transparent adhesive layer 112 is composed of an adhesive that does not contain light-diffusing particles. In addition, "does not contain light-diffusing particles" means "almost does not contain light-diffusing particles", and in addition to not containing light-diffusing particles at all, it also includes the case where the light-diffusing particles are contained in an amount that does not impair the effect of the present embodiment. The amount of the light-diffusing particles is preferably 0.1% by mass or less, particularly preferably 0.01% by mass or less, further preferably 0.001% by mass or less, and most preferably 0% by mass.
[0079] As long as at least one of the light-diffusing adhesive layer 111 and the transparent adhesive layer 112 is composed of an active energy ray-curable adhesive, the type of adhesive constituting the light-diffusing adhesive layer 111 and the transparent adhesive layer 112 of the adhesive sheet 1 of the present embodiment is not particularly limited. For example, it can be any one of an acrylic adhesive, a polyester adhesive, a polyurethane adhesive, a rubber adhesive, a silicone adhesive, etc. In addition, the adhesive can be any one of an emulsion type, a solvent type or a solvent-free type, and can also be any one of a cross-linked type or a non-cross-linked type. Among them, an acrylic adhesive with excellent adhesive properties, optical properties, etc. is preferred. As an acrylic adhesive, it is preferably a cross-linked type, and it is further preferably a thermal cross-linked type.
[0080] The adhesive constituting the light-diffusing adhesive layer 111 and the adhesive constituting the transparent adhesive layer 112 can be the same kind or different kinds, but preferably all are active energy ray-curable adhesives, and particularly preferably all are active energy ray-curable acrylic adhesives. Thus, excellent anti-foaming property can be brought into play. At this time, the composition except the light-diffusing particles can be the same or different. In addition, the monomer composition of the main polymer can be the same or different. In addition, as the adhesive constituting the light-diffusing adhesive layer 111 and the adhesive constituting the transparent adhesive layer 112, one of them can be an active energy ray-curable acrylic adhesive, and the other can be an inactive energy ray-curable acrylic adhesive.
[0081] Hereinafter, the case where both the adhesive constituting the light-diffusing adhesive layer 111 and the adhesive constituting the transparent adhesive layer 112 are active energy ray-curable acrylic adhesives will be described, but the present invention is not limited thereto.
[0082] From the perspective of further enhancing the cohesive force of the polymers, the adhesive constituting the light-diffusing adhesive layer 111 and the adhesive constituting the transparent adhesive layer 112 are preferably formed by cross-linking an adhesive composition (hereinafter sometimes referred to as "adhesive composition P") containing a (meth) acrylate polymer (A), a crosslinking agent (B) and an active energy ray curable component (C). In the case of the light-diffusing adhesive layer 111, the adhesive composition P further contains light-diffusing particles (D). If it is an adhesive composition P with the above composition, it is easy to meet the above storage modulus, gel fraction, haze value, and adhesion, etc.
[0083] The adhesive obtained by the adhesive composition P can exert excellent optical properties, adhesion, step tracking, etc. In addition, in this specification, (meth) acrylic acid refers to both acrylic acid and methacrylic acid. Other similar terms are also the same. In addition, the concept of "copolymer" is also included in "polymer".
[0084] (1) Components of the adhesive composition
[0085] (1-1) (Meth)acrylate polymer (A)
[0086] The (meth)acrylate polymer (A) of the present embodiment preferably contains a reactive group-containing monomer as a monomer unit constituting the polymer, and the reactive group-containing monomer has a reactive group in the molecule that reacts with the crosslinking agent (B). By reacting the reactive group from the reactive group-containing monomer with the crosslinking agent (B), a crosslinked structure (three-dimensional network structure) can be formed, and an adhesive having a desired cohesive force can be obtained.
[0087] Preferred examples of the reactive group-containing monomer include monomers having a hydroxyl group in the molecule (hydroxyl group-containing monomers), monomers having a carboxyl group in the molecule (carboxyl group-containing monomers), monomers having an amino group in the molecule (amino group-containing monomers), etc. Among them, hydroxyl group-containing monomers or carboxyl group-containing monomers having excellent reactivity with the crosslinking agent (B) are preferred.
[0088] As the hydroxyl-containing monomer, for example, 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 3-hydroxybutyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate and other hydroxyalkyl (meth)acrylates, etc. can be cited. Among them, from the point of view of the reactivity of the hydroxyl group in the obtained (meth)acrylate polymer (A) with the crosslinking agent (B) and the copolymerizability with other monomers, hydroxyalkyl (meth)acrylates having a hydroxyalkyl group with 1 to 4 carbon atoms are preferred. Specifically, for example, 2-hydroxyethyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate and the like can be preferably cited, and 2-hydroxyethyl acrylate or 4-hydroxybutyl acrylate can be particularly preferably cited. These hydroxyl-containing monomers can be used alone or in combination of two or more.
[0089] Examples of carboxyl-containing monomers include ethylenically unsaturated carboxylic acids such as acrylic acid, methacrylic acid, crotonic acid, maleic acid, itaconic acid, and citraconic acid. Among them, acrylic acid is preferred from the perspective of the reactivity of the carboxyl group in the obtained (meth)acrylate polymer (A) with the crosslinking agent (B) and copolymerizability with other monomers. These carboxyl-containing monomers may be used alone or in combination of two or more.
[0090] As the amino-containing monomer, for example, aminoethyl (meth)acrylate, n-butylaminoethyl (meth)acrylate, etc. can be cited. These amino-containing monomers can be used alone or in combination of two or more. In addition, the nitrogen atom-containing monomer described later is excluded from the amino-containing monomer.
[0091] In (meth) acrylate polymer (A), as the monomer unit constituting the polymer, according to the following limit, preferably contains more than 5% by mass, particularly preferably contains more than 10% by mass, and further preferably contains more than 15% by mass of reactive group-containing monomers. In addition, in (meth) acrylate polymer (A), as the monomer unit constituting the polymer, according to the upper limit, preferably contains less than 40% by mass, particularly preferably contains less than 30% by mass, and further preferably contains less than 25% by mass of reactive group-containing monomers. If (meth) acrylate polymer (A) contains reactive group-containing monomers as monomer units in the above-mentioned amount, a good cross-linked structure can be formed in the obtained adhesive, and it becomes easy to obtain the desired gel fraction and storage modulus. In addition, when containing light-diffusing particles (D), the dispersibility of the light-diffusing particles (D) in the obtained adhesive has a tendency to become good.
[0092] In addition, (meth) acrylate polymer (A) also preferably does not contain carboxyl-containing monomers as monomer units constituting the polymer. Since carboxyl is an acid component, by not containing carboxyl-containing monomers, even if there are substances that produce adverse conditions due to acid on the attachment object of the adhesive, such as transparent conductive films or metal films such as tin-doped indium oxide (ITO), the above-mentioned adverse conditions (corrosion, resistance value changes, etc.) caused by acid can be suppressed. However, it is also allowed to contain a specified amount of carboxyl-containing monomers to the extent that the above-mentioned adverse conditions are not produced. Specifically, in (meth) acrylate polymer (A), as a monomer unit, it is allowed to contain carboxyl-containing monomers in an amount of less than 0.1% by mass, preferably in an amount of less than 0.01% by mass, and further preferably in an amount of less than 0.001% by mass.
[0093] The (meth)acrylate polymer (A) preferably contains an alkyl (meth)acrylate as a monomer unit constituting the polymer. This can exhibit good adhesiveness and at the same time can induce a lower storage modulus of the resulting adhesive. The alkyl group may be linear or branched.
[0094] From the viewpoint of adhesiveness, the alkyl (meth)acrylate is preferably an alkyl (meth)acrylate having an alkyl group with 1 to 20 carbon atoms. Examples of the alkyl (meth)acrylate having an alkyl group with 1 to 20 carbon atoms include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, n-butyl (meth)acrylate, n-pentyl (meth)acrylate, n-hexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, isooctyl (meth)acrylate, n-decyl (meth)acrylate, n-dodecyl (meth)acrylate, tetradecyl (meth)acrylate, hexadecyl (meth)acrylate, and octadecyl (meth)acrylate. Among them, from the perspective of further improving the adhesiveness or inducing the storage modulus to be lower, the (meth) alkyl esters having 4 to 8 carbon atoms in the alkyl group are preferred, and n-butyl (meth) acrylate, 2-ethylhexyl (meth) acrylate, or isooctyl (meth) acrylate are particularly preferred, and n-butyl acrylate, 2-ethylhexyl acrylate, or isooctyl acrylate is further preferred. In addition, these alkyl (meth) acrylates may be used alone or in combination of two or more.
[0095] In the (meth) acrylate polymer (A), as a monomer unit constituting the polymer, it is preferred to contain 45% by mass or more, particularly preferably 55% by mass or more, and further preferably 65% by mass or more of (meth) alkyl acrylate. If the lower limit of the content of the (meth) alkyl acrylate is as described above, the (meth) acrylate polymer (A) can exert suitable adhesion. In addition, when light-diffusing particles (D) are contained, there is a tendency to make the dispersibility of the light-diffusing particles (D) in the adhesive good, which can inhibit the required adhesion of the (meth) acrylate polymer (A) from being damaged. On the other hand, in the (meth) acrylate polymer (A), as a monomer unit constituting the polymer, it is preferred to contain 99% by mass or less, more preferably 95% by mass or less, particularly preferably 90% by mass or less, and further preferably 75% by mass or less of (meth) alkyl acrylate. If the upper limit of the content of the (meth) alkyl acrylate is as described above, other monomer components such as a monomer containing a reactive functional group can be introduced into the (meth) acrylate polymer (A) in an appropriate amount.
[0096] The (meth)acrylate polymer (A) also preferably contains a monomer having an alicyclic structure in the molecule (alicyclic structure-containing monomer) as a monomer unit constituting the polymer. The alicyclic structure-containing monomer increases the glass transition temperature of the polymer and increases the storage modulus of the resulting adhesive. In addition, since the alicyclic structure-containing monomer has a large volume, it is presumed that by making it present in the polymer, the interval between the polymers is enlarged, the coating solution viscosity is reduced, and the thick film of the adhesive layer becomes easy.
[0097] The carbon ring of the alicyclic structure in the alicyclic structure-containing monomer may be a saturated structure or may have an unsaturated bond in part. In addition, the alicyclic structure may be a monocyclic alicyclic structure or a polycyclic alicyclic structure such as a bicyclic or tricyclic structure. From the perspective of adjusting the storage modulus of the obtained adhesive to be higher and at the same time thickening the adhesive layer, the alicyclic structure is preferably a polycyclic alicyclic structure (polycyclic structure). Further, considering the compatibility of the (meth)acrylate polymer (A) with other components, the polycyclic structure is particularly preferably a bicyclic to tetracyclic structure. In addition, as described above, from the perspective of improving the storage modulus or thickening, the number of carbon atoms in the alicyclic structure (referring to the total number of carbon atoms in the part forming the ring, and when multiple rings exist independently, it refers to the total number of carbon atoms) is generally preferably 5 or more, and particularly preferably 7 or more. On the other hand, although the upper limit of the number of carbon atoms in the alicyclic structure is not particularly limited, it is preferably 15 or less, and particularly preferably 10 or less from the same perspective as described above.
[0098] As the above-mentioned alicyclic structure-containing monomer, specifically, cyclohexyl (meth)acrylate, dicyclopentyl (meth)acrylate, adamantyl (meth)acrylate, isobornyl (meth)acrylate, dicyclopentenyl (meth)acrylate, dicyclopentenyloxyethyl (meth)acrylate, etc. can be listed. Among them, dicyclopentyl (meth)acrylate (carbon number of alicyclic structure: 10), adamantyl (meth)acrylate (carbon number of alicyclic structure: 10) or isobornyl (meth)acrylate (carbon number of alicyclic structure: 7) which exhibits more excellent step followability is preferred, isobornyl (meth)acrylate is particularly preferred, and isobornyl acrylate is further preferred. These alicyclic structure-containing monomers can be used alone or in combination of two or more.
[0099] When the (meth)acrylate polymer (A) contains an alicyclic structure-containing monomer as a monomer unit constituting the polymer, from the perspective of adjusting the storage modulus of the obtained adhesive to a preferred range, it is preferably 1% by mass or more, particularly preferably 5% by mass or more, and further preferably 10% by mass or more of the alicyclic structure-containing monomer. In addition, from the same perspective as above, the content of the alicyclic structure-containing monomer is preferably set to 25% by mass or less, particularly preferably 20% by mass or less, and further preferably 15% by mass or less.
[0100] The above-mentioned (meth)acrylate polymer (A) also preferably contains a nitrogen atom-containing monomer as a monomer unit constituting the polymer. By allowing the nitrogen atom-containing monomer to exist in the polymer as a structural unit, the adhesive can be given a predetermined polarity, so that the adhesive has excellent affinity even for an adherend having a certain degree of polarity such as glass. From the perspective of giving the (meth)acrylate polymer (A) moderate rigidity, the above-mentioned nitrogen atom-containing monomer is preferably a monomer having a nitrogen-containing heterocycle. In addition, from the perspective of increasing the degree of freedom of the part from the above-mentioned nitrogen atom-containing monomer in the high-dimensional structure of the constituted adhesive, it is preferred that the nitrogen atom-containing monomer does not contain a reactive unsaturated double bond group except for a polymerizable group used in the polymerization for forming the (meth)acrylate polymer (A).
[0101] As monomers having nitrogen-containing heterocyclic rings, for example, N-(methyl)acryloylmorpholine, N-vinyl-2-pyrrolidone, N-(methyl)acryloylpyrrolidone, N-(methyl)acryloylpiperidine, N-(methyl)acryloylpyrrolidine, N-(methyl)acryloylaziridine, aziridinylethyl(methyl)acrylate, 2-vinylpyridine, 4-vinylpyridine, 2-vinylpyrazine, 1-vinylimidazole, N-vinylcarbazole, N-vinylphthalimide, etc., among which N-(methyl)acryloylmorpholine having better adhesion is preferred, and N-acryloylmorpholine is particularly preferred. These nitrogen-containing heterocyclic monomers can be used alone or in combination of two or more.
[0102] When the (meth)acrylate polymer (A) contains a nitrogen atom-containing monomer as a monomer unit constituting the polymer, it is preferably 1% by mass or more, particularly preferably 2% by mass or more, and further preferably 4% by mass or more of the nitrogen atom-containing monomer. In addition, the (meth)acrylate polymer (A) preferably contains 24% by mass or less, particularly preferably 16% by mass or less, and further preferably 8% by mass or less of the nitrogen atom-containing monomer as a monomer unit constituting the polymer. If the content of the nitrogen atom-containing monomer is within the above range, the obtained adhesive can fully exert excellent adhesion to glass.
[0103] As required, the (meth)acrylate polymer (A) may also contain other monomers as monomer units constituting the polymer. In order not to hinder the above-mentioned effects of the monomer containing reactive functional groups, as other monomers, monomers containing no reactive functional groups are preferably used. As such monomers, for example, (meth)acrylic acid alkoxyalkyl esters such as methoxyethyl (meth)acrylate and ethoxyethyl (meth)acrylate, vinyl acetate, styrene, etc. can be cited. These other monomers can be used alone or in combination of two or more.
[0104] The (meth)acrylate polymer (A) is preferably a linear polymer, because by making it a linear polymer, molecular chains are easily entangled with each other and the cohesive force can be expected to be improved, so that it is easy to obtain an adhesive with excellent step tracking properties and anti-foaming properties under high temperature and high humidity conditions.
[0105] In addition, the (meth)acrylate polymer (A) is preferably a solution polymer obtained by solution polymerization. Since a solution polymer can easily obtain a high molecular weight polymer and improve the cohesive force, it is easy to obtain an adhesive with excellent step tracking and anti-foaming properties under high temperature and high humidity conditions.
[0106] The polymerization form of the (meth)acrylate polymer (A) may be a random copolymer or a block copolymer.
[0107] The weight average molecular weight of (methyl) acrylate polymer (A) is preferably more than 200,000, more preferably more than 300,000, and particularly preferably more than 400,000. Thus, the storage modulus and gel fraction of the obtained adhesive can be improved so that the step tracking property under high temperature and high humidity conditions becomes more excellent. In addition, the weight average molecular weight is further preferably more than 500,000. Thus, even in the adhesive containing light-diffusing particles (D), a high storage modulus of the degree of sufficient cohesive force can be obtained. And, there is a tendency that the dispersibility of the light-diffusing particles (D) in the adhesive can be made good.
[0108] In addition, the upper limit of the weight average molecular weight of (meth) acrylate polymer (A) is preferably less than 1.5 million, more preferably less than 1.2 million, particularly preferably less than 1 million, and more preferably less than 800,000. If the upper limit of the weight average molecular weight of (meth) acrylate polymer (A) is above, the value of the storage modulus of the obtained adhesive is easy to become a suitable value, and the initial step tracking property becomes more excellent. The weight average molecular weight in this specification is the value converted by standard polystyrene measured by gel permeation chromatography (GPC) method.
[0109] In the adhesive composition P, the (meth)acrylate polymer (A) may be used alone or in combination of two or more.
[0110] (1-2) Cross-linking agent (B)
[0111] As the crosslinking agent (B), any substance that reacts with the reactive group possessed by the (meth) acrylate polymer (A) may be used, for example, isocyanate crosslinking agents, epoxy crosslinking agents, amine crosslinking agents, melamine crosslinking agents, aziridine crosslinking agents, hydrazine crosslinking agents, aldehyde crosslinking agents, oxazoline crosslinking agents, metal alkoxide crosslinking agents, metal chelate crosslinking agents, metal salt crosslinking agents, ammonium salt crosslinking agents, etc. Among the above, it is preferred to use an isocyanate crosslinking agent with excellent reactivity with a hydroxyl group and a carboxyl group, or an epoxy crosslinking agent with excellent reactivity with a carboxyl group. In addition, the crosslinking agent (B) may be used alone or in combination of two or more.
[0112] The isocyanate crosslinking agent contains at least a polyisocyanate compound. Examples of the polyisocyanate compound include aromatic polyisocyanates such as toluene diisocyanate, diphenylmethane diisocyanate, and xylene diisocyanate, aliphatic polyisocyanates such as hexamethylene diisocyanate, alicyclic polyisocyanates such as isophorone diisocyanate and hydrogenated diphenylmethane diisocyanate, and biuret bodies and isocyanurate bodies of these substances, and adducts thereof as reactants with low molecular weight active hydrogen-containing compounds such as ethylene glycol, propylene glycol, neopentyl glycol, trimethylolpropane, and castor oil. Among them, from the perspective of reactivity with hydroxyl groups, trimethylolpropane-modified aromatic polyisocyanates are preferred, and trimethylolpropane-modified toluene diisocyanate and trimethylolpropane-modified xylene diisocyanate are particularly preferred.
[0113] Examples of epoxy crosslinking agents include 1,3-bis(N,N-diglycidylaminomethyl)cyclohexane, N,N,N',N'-tetraglycidyl-m-xylene diamine, ethylene glycol diglycidyl ether, 1,6-hexanediol diglycidyl ether, trimethylolpropane diglycidyl ether, diglycidyl aniline, diglycidylamine, etc. Among them, 1,3-bis(N,N-diglycidylaminomethyl)cyclohexane is preferred from the viewpoint of reactivity with carboxyl groups.
[0114] Relative to 100 parts by mass of (meth) acrylate polymer (A), the content of the crosslinking agent (B) in the adhesive composition P is preferably more than 0.01 parts by mass, particularly preferably more than 0.05 parts by mass, and more preferably more than 0.1 parts by mass. In addition, the content is preferably less than 10 parts by mass, more preferably less than 5 parts by mass, particularly preferably less than 1 part by mass, more preferably less than 0.4 parts by mass, and most preferably less than 0.2 parts by mass. By making the content of the crosslinking agent (B) within the above range, the storage modulus, gel fraction, adhesion, etc. of the obtained adhesive are easily suitable.
[0115] (1-3) Active energy ray-curable component (C)
[0116] It is speculated that in the adhesive obtained by curing the adhesive composition P containing the active energy ray curable component (C) by crosslinking, the active energy ray curable components (C) are polymerized with each other, and the polymerized active energy ray curable components (C) are entangled in the crosslinked structure (three-dimensional network structure) of the (meth)acrylate polymer (A). The adhesive having this high-dimensional structure can improve the storage modulus and gel fraction to a certain extent, and has particularly excellent step tracking properties under high temperature and high humidity conditions.
[0117] The active energy ray-curable component (C) is not particularly limited as long as it can be cured by irradiation with active energy rays to obtain the above-mentioned effect, and can be any one of a monomer, an oligomer or a polymer, or a mixture thereof. Among them, a multifunctional acrylate monomer having a more excellent anti-foaming property can be preferably cited.
[0118] Examples of the polyfunctional acrylate monomer include 1,4-butanediol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, neopentyl glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, adipate neopentyl glycol di(meth)acrylate, hydroxypivalate neopentyl glycol di(meth)acrylate, dicyclopentyl di(meth)acrylate, tricyclodecane dimethanol (meth)acrylate, caprolactone-modified dicyclopentenyl di(meth)acrylate, ethylene oxide-modified phosphoric acid di(meth)acrylate, di(acryloyloxyethyl) isocyanurate, allylated cyclohexyl di(meth)acrylate, ethoxylated bisphenol A diacrylate, 9,9-bis[4-(2-acryloyloxyethoxy)]
[0043] The present invention relates to a difunctional monomer such as trimethylolpropane tri(meth)acrylate, dipentaerythritol tri(meth)acrylate, propionic acid-modified dipentaerythritol tri(meth)acrylate, pentaerythritol tri(meth)acrylate, propylene oxide-modified trimethylolpropane tri(meth)acrylate, tri(acryloyloxyethyl)isocyanurate, ε-caprolactone-modified tri-(2-(meth)acryloyloxyethyl)isocyanurate, etc.; a tetrafunctional monomer such as diglycerol tetra(meth)acrylate, pentaerythritol tetra(meth)acrylate, etc.; a pentafunctional monomer such as propionic acid-modified dipentaerythritol penta(meth)acrylate, etc.; a hexafunctional monomer such as dipentaerythritol hexa(meth)acrylate, caprolactone-modified dipentaerythritol hexa(meth)acrylate, etc. These multifunctional acrylate monomers may be used alone or in combination of two or more. Furthermore, from the viewpoint of compatibility with the (meth)acrylate polymer (A), the polyfunctional acrylate monomer is preferably a polyfunctional acrylate monomer having a molecular weight of less than 1,000.
[0119] From the perspective of making the storage modulus value of the adhesive after irradiation with active energy rays and the storage modulus change rate ΔG' before and after curing suitable values, and the step tracking property under high temperature and high humidity conditions is more excellent, the lower limit of the content of the active energy ray-curable component (C) in the adhesive composition P is preferably 1 mass part or more, particularly preferably 3 mass parts or more, and more preferably 4 mass parts or more relative to 100 mass parts of the (meth)acrylate polymer (A). On the other hand, from the perspective of the adhesive force of the adhesive after irradiation with active energy rays, the upper limit of the above content is preferably 20 mass parts or less, particularly preferably 12 mass parts or less, and more preferably 8 mass parts or less.
[0120] (1-4) Light-diffusing particles (D)
[0121] The light-diffusing fine particles (D) may be any material as long as they can make the light-diffusing adhesive layer 111 and the composite adhesive layer 11 satisfy the above-mentioned physical properties.
[0122] As light-diffusing particles (D), for example, inorganic particles such as silicon dioxide, calcium carbonate, aluminum hydroxide, magnesium hydroxide, clay, talc, titanium dioxide, etc. can be listed; organic light-transmitting particles such as acrylic resin, polystyrene resin, polyethylene resin, epoxy resin, etc.; particles composed of silicon-containing compounds such as silicone resin having a structure between inorganic and organic (for example, Tospearl series manufactured by Momentive Performance Materials Japan Inc.), etc. Among them, particles composed of silicone resin are preferred. As a result, the adhesive sheet can easily meet the above-mentioned haze value and image clarity. The above light-diffusing particles (D) can be used alone or in combination of two or more.
[0123] As the shape of the light-diffusing particles (D), spherical particles with uniform light diffusion are preferred. The lower limit of the average particle size of the light-diffusing particles (D) based on the centrifugal sedimentation light transmission method is preferably 1.0 μm or more, particularly preferably 2.0 μm or more, and more preferably 3.0 μm or more. If the lower limit of the above-mentioned average particle size is as above, it is easy to show the desired haze. On the other hand, the upper limit of the above-mentioned average particle size is preferably 10 μm or less, particularly preferably 8 μm or less, and more preferably 6 μm or less. If the upper limit of the above-mentioned average particle size is as above, it is easy to prevent the haze value from becoming too high, and a high-precision display image can be well displayed.
[0124] The average particle size by the centrifugal sedimentation light transmission method is a value measured by using a centrifugal automatic particle size distribution analyzer (CAPA-700 manufactured by HORIBA, Ltd.) to prepare a sample prepared by fully stirring 1.2 g of fine particles and 98.8 g of isopropyl alcohol as a measurement sample.
[0125] The content of the light-diffusing particles (D) in the adhesive composition P is as long as it can satisfy the above-mentioned physical properties. Specifically, the content of the light-diffusing particles (D) is preferably 1% by mass or more, more preferably 3% by mass or more, particularly preferably 6% by mass or more, and further preferably 8% by mass or more. In addition, the content of the light-diffusing particles (D) is preferably 50% by mass or less, more preferably 40% by mass or less, particularly preferably 30% by mass or less, and further preferably 25% by mass or less. By making the content of the light-diffusing particles (D) within the above range, it becomes easy to satisfy the above-mentioned haze value, storage modulus and adhesion.
[0126] (1-5) Photopolymerization initiator (E)
[0127] When ultraviolet rays are used as active energy rays for curing the adhesive composition P, it is preferred that the adhesive composition P further contains a photopolymerization initiator (E). Thus, by containing the photopolymerization initiator (E), the active energy ray-curable component (C) can be efficiently polymerized, and the polymerization curing time and the irradiation amount of the active energy rays can be reduced.
[0128] Examples of such a photopolymerization initiator (E) include benzoin, benzoin methyl ether, benzoin ethyl ether, benzoin isopropyl ether, benzoin n-butyl ether, benzoin isobutyl ether, acetophenone, dimethylaminoacetophenone, 2,2-dimethoxy-2-phenylacetophenone, 2,2-diethoxy-2-phenylacetophenone, 2-hydroxy-2-methyl-1-phenylpropane-1-one, 1-hydroxycyclohexyl phenyl ketone, 2-methyl-1-[4-(methylthio)phenyl]-2-morpholinyl-1-propanone, 4-(2-hydroxyethoxy)phenyl-2-(hydroxy-2-propyl)ketone, benzophenone, p-phenylenediol, Ketone, 4,4'-diethylaminobenzophenone, dichlorobenzophenone, 2-methylanthraquinone, 2-ethylanthraquinone, 2-tert-butylanthraquinone, 2-aminoanthraquinone, 2-methylthioxanthone, 2-ethylthioxanthone, 2-chlorothioxanthone, 2,4-dimethylthioxanthone, 2,4-diethylthioxanthone, benzyl dimethyl ketal, acetophenone dimethyl ketal, p-dimethylaminobenzoate, oligo[2-hydroxy-2-methyl-1[4-(1-methylvinyl)phenyl]acetone], 2,4,6-trimethylbenzoyl-diphenyl-phosphine oxide, bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxide, etc. These photopolymerization initiators may be used alone or in combination of two or more.
[0129] Among the above, phosphine oxide-based photopolymerization initiators are preferred because they are easily decomposed even when irradiated with ultraviolet rays through a plastic plate containing an ultraviolet absorber, and the adhesive is easily cured. Specifically, 2,4,6-trimethylbenzoyl-diphenyl-phosphine oxide, bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxide, and the like are preferred.
[0130] The lower limit of the content of the photopolymerization initiator (E) in the adhesive composition P is preferably 0.1 parts by mass or more, particularly preferably 1 part by mass or more, and further preferably 5 parts by mass or more, relative to 100 parts by mass of the active energy ray-curable component (C). In addition, the upper limit is preferably 30 parts by mass or less, particularly preferably 20 parts by mass or less, and further preferably 12 parts by mass or less.
[0131] (1-6) Various additives
[0132] As required, various additives commonly used in acrylic adhesives may be added to the adhesive composition P, such as silane coupling agents, rust inhibitors, ultraviolet absorbers, antistatic agents, tackifiers, antioxidants, light stabilizers, softeners, refractive index adjusters, etc. In addition, the polymerization solvent and dilution solvent described below are not included in the additives constituting the adhesive composition P.
[0133] In the above, the adhesive composition P preferably contains a silane coupling agent. This improves adhesion to the adherend, whether it is a plastic plate or a glass member, and further improves step tracking and anti-foaming properties under high temperature and high humidity conditions.
[0134] As the silane coupling agent, an organosilicon compound which has good compatibility with the (meth)acrylate polymer (A), is light-transmissive and has at least one alkoxysilyl group in the molecule is preferred.
[0135] Examples of the silane coupling agent include silicon compounds containing polymerizable unsaturated groups such as vinyl trimethoxysilane, vinyl triethoxysilane, and methacryloxypropyl trimethoxysilane; silicon compounds having epoxy structures such as 3-glycidyloxypropyl trimethoxysilane and 2-(3,4-epoxycyclohexyl)ethyl trimethoxysilane; and silicon compounds containing mercapto groups such as 3-mercaptopropyl trimethoxysilane, 3-mercaptopropyl triethoxysilane, and 3-mercaptopropyl dimethoxymethylsilane. Silicon compounds containing amino groups such as 3-aminopropyltrimethoxysilane, N-(2-aminoethyl)-3-aminopropyltrimethoxysilane, and N-(2-aminoethyl)-3-aminopropylmethyldimethoxysilane; condensates of 3-chloropropyltrimethoxysilane, 3-isocyanopropyltriethoxysilane, or at least one of them and methyltriethoxysilane, ethyltriethoxysilane, methyltrimethoxysilane, and ethyltrimethoxysilane, etc. These silane coupling agents can be used alone or in combination of two or more.
[0136] The content of the silane coupling agent in the adhesive composition P is preferably 0.01 parts by mass or more, particularly preferably 0.05 parts by mass or more, and further preferably 0.1 parts by mass or more relative to 100 parts by mass of the (meth)acrylate polymer (A). In addition, the content is preferably 1.2 parts by mass or less, particularly preferably 0.8 parts by mass or less, and further preferably 0.4 parts by mass or less.
[0137] (2) Preparation of adhesive composition
[0138] The adhesive composition P can be prepared by preparing a (meth)acrylate polymer (A), mixing the obtained (meth)acrylate polymer (A), a crosslinking agent (B) and an active energy ray-curable component (C), and adding a photopolymerization initiator (E), additives, etc. as needed. In the case of the light-diffusing adhesive layer 111, light-diffusing fine particles (D) may be further mixed.
[0139] The (meth)acrylate polymer (A) can be prepared by polymerizing the mixture of monomers constituting the polymer using a conventional free radical polymerization method. The polymerization of the (meth)acrylate polymer (A) is preferably carried out by a solution polymerization method using a polymerization initiator as required. However, the present invention is not limited thereto, and polymerization can also be carried out without a solvent. As the polymerization solvent, for example, ethyl acetate, n-butyl acetate, isobutyl acetate, toluene, acetone, hexane, methyl ethyl ketone, etc. can be listed, and two or more thereof can also be used simultaneously.
[0140] Examples of the polymerization initiator include azo compounds and organic peroxides, and two or more thereof may be used simultaneously. Examples of the azo compounds include 2,2'-azobisisobutyronitrile, 2,2'-azobis(2-methylbutyronitrile), 1,1'-azobis(cyclohexane-1-carbonitrile), 2,2'-azobis(2,4-dimethylvaleronitrile), 2,2'-azobis(2,4-dimethyl-4-methoxyvaleronitrile), dimethyl 2,2'-azobis(2-methylpropionate), 4,4'-azobis(4-cyanovaleric acid), 2,2'-azobis(2-hydroxymethylpropionitrile), 2,2'-azobis(2-hydroxymethylpropionitrile), and 2,2'-azobis[2-(2-imidazolin-2-yl)propane].
[0141] Examples of the organic peroxide include benzoyl peroxide, tert-butyl perbenzoate, cumene hydroperoxide, diisopropyl peroxydicarbonate, di-n-propyl peroxydicarbonate, di(2-ethoxyethyl) peroxydicarbonate, tert-butyl peroxyneodecanoate, tert-butyl peroxypivalate, (3,5,5-trimethylhexanoyl) peroxide, dipropionyl peroxide, and diacetyl peroxide.
[0142] Furthermore, in the above-mentioned polymerization step, by adding a chain transfer agent such as 2-mercaptoethanol, the weight average molecular weight of the obtained polymer can be adjusted.
[0143] After obtaining the (meth)acrylate polymer (A), a crosslinking agent (B), an active energy ray curable component (C), and a diluting solvent as required, light diffusing particles (D), a photopolymerization initiator (E), additives, etc. are added to the solution of the (meth)acrylate polymer (A), and the mixture is fully mixed to obtain a solvent-diluted adhesive composition P (coating solution). In addition, for any of the above components, when a solid substance is used, or when precipitation occurs when mixed with other components in an undiluted state, the component can be dissolved or diluted in a diluting solvent alone in advance and then mixed with other components.
[0144] As the above-mentioned dilution solvent, for example, aliphatic hydrocarbons such as hexane, heptane, and cyclohexane; aromatic hydrocarbons such as toluene and xylene; halogenated hydrocarbons such as dichloromethane and vinyl chloride; alcohols such as methanol, ethanol, propanol, butanol, and 1-methoxy-2-propanol; ketones such as acetone, methyl ethyl ketone, 2-pentanone, isophorone, and cyclohexanone; esters such as ethyl acetate and butyl acetate; cellosolve-type solvents such as ethyl cellosolve, etc. can be used.
[0145] The concentration and viscosity of the coating solution thus prepared are not particularly limited as long as they are within the range that can be coated, and can be appropriately selected according to the situation. For example, the adhesive composition P is diluted in a manner such that the concentration is 10 to 60% by mass. In addition, when obtaining the coating solution, the addition of a diluting solvent or the like is not a necessary condition. If the adhesive composition P is a viscosity that can be coated, the diluting solvent may not be added. At this time, the adhesive composition P is a coating solution in which the polymerization solvent of the (meth)acrylate polymer (A) is directly used as the diluting solvent.
[0146] (3) Formation of Adhesive Layer
[0147] Preferably, the light diffusion adhesive layer 111 and the transparent adhesive layer 112 of the present embodiment are respectively composed of an adhesive formed by crosslinking the adhesive composition P (coating layer). The crosslinking of the adhesive composition P can usually be carried out by heat treatment. In addition, the drying process when the diluting solvent etc. is volatilized from the coating layer of the adhesive composition P applied on the required object can also be used as the heat treatment.
[0148] The heating temperature of the heat treatment is preferably 50 to 150° C., particularly preferably 70 to 120° C. The heating time is preferably 10 seconds to 10 minutes, particularly preferably 50 seconds to 2 minutes.
[0149] After the heat treatment, a 1-2 week aging period may be provided at room temperature (e.g., 23° C., 50% RH) as needed. If the aging period is required, the adhesive is formed after the aging period. If the aging period is not required, the adhesive is formed directly after the heat treatment.
[0150] By the above-mentioned heat treatment (and aging), the (meth)acrylate polymer (A) is sufficiently crosslinked via the crosslinking agent (B).
[0151] The composite adhesive layer 11 of this embodiment can be obtained by laminating a light-diffusing adhesive layer 111 and a transparent adhesive layer 112. The timing of lamination can be before or after aging each adhesive layer. However, in order to further improve the adhesion of the light-diffusing adhesive layer 111 and the transparent adhesive layer 112, it is preferred to laminate each adhesive layer before aging.
[0152] 1-2. Peel off sheet
[0153] The release sheets 12a and 12b protect the composite adhesive layer 11 until the adhesive sheet 1 is used, and are peeled off when the adhesive sheet 1 (composite adhesive layer 11) is used. In the adhesive sheet 1 of the present embodiment, one or both of the release sheets 12a and 12b are not essential.
[0154] As the peeling sheets 12a and 12b, for example, polyethylene film, polypropylene film, polybutylene film, polybutadiene film, polymethylpentene film, polyvinyl chloride film, vinyl chloride copolymer film, polyethylene terephthalate film, polyethylene naphthalate film, polybutylene terephthalate film, polyurethane film, ethylene-vinyl acetate film, ionomer resin film, ethylene-(methyl) acrylic acid copolymer film, ethylene-(methyl) acrylic acid ester copolymer film, polystyrene film, polycarbonate film, polyimide film, fluororesin film, etc. can be used. In addition, cross-linked films of these films can also be used. Further, laminated films of these films can also be used.
[0155] The release surfaces of the release sheets 12a and 12b (particularly the surfaces in contact with the composite adhesive layer 11) are preferably subjected to a release treatment. Examples of release agents used for the release treatment include alkyd, silicone, fluorine, unsaturated polyester, polyolefin, and wax release agents.
[0156] The thickness of the release sheets 12a and 12b is not particularly limited, but is generally about 20 to 150 μm.
[0157] 2. Manufacturing of adhesive sheet
[0158] As a manufacturing example of the adhesive sheet 1, a coating solution of an adhesive composition P for forming a transparent adhesive layer 112 is applied to the release surface of a release sheet 12a, and a heat treatment is performed to thermally crosslink the adhesive composition P to form a coating layer, thereby obtaining a release sheet 12a with a coating layer. In addition, a coating solution of an adhesive composition P for forming a light-diffusing adhesive layer 111 is applied to the release surface of another release sheet 12b, and a heat treatment is performed to thermally crosslink the adhesive composition P to form a coating layer, thereby obtaining a release sheet 12b with a coating layer. Then, the release sheet 12a with a coating layer and the release sheet 12b with a coating layer are laminated in such a manner that the two coating layers are in contact with each other. Here, a plurality of release sheets with coating layers can be prepared, and the required number of layers of the coating layer can be laminated in a required stacking order. When a ripening period is required, the laminated coating layer becomes the composite adhesive layer 11 by setting the ripening period, and when a ripening period is not required, the laminated coating layer directly becomes the composite adhesive layer 11. Thus, the adhesive sheet 1 having the composite adhesive layer 11 is obtained, and the composite adhesive layer 11 is a laminate of the light diffusing adhesive layer 111 and the transparent adhesive layer 112. The conditions for the heat treatment and ripening are as described above.
[0159] In addition, the coating layer for forming the transparent adhesive layer 112 and the coating layer for forming the light-diffusing adhesive layer 111 can be clamped by two peeling sheets respectively. When the coating layer for forming the transparent adhesive layer 112 and the coating layer for forming the light-diffusing adhesive layer 111 are attached, one peeling sheet can be peeled off respectively.
[0160] As a method for applying the coating solution of the adhesive composition P, for example, a bar coating method, a knife coating method, a roll coating method, a blade coating method, a die coating method, a gravure coating method, etc. can be utilized.
[0161] [Optical laminate]
[0162] An optical laminate according to one embodiment of the present invention comprises an optical member, another optical member, and a cured composite adhesive layer for bonding the optical member and the other optical member to each other. The cured composite adhesive layer is a layer cured by irradiating the composite adhesive layer of the adhesive sheet according to the above embodiment with active energy rays.
[0163] At least one of the one optical member and the other optical member may have a step (convexo-concave) on the surface on the side bonded by the cured composite adhesive layer. In this case, the transparent adhesive layer of the cured composite adhesive layer is preferably in contact with the step.
[0164] The optical layered body of the present embodiment may be a display body itself or a member constituting a part of the display body. In addition, the optical layered body is not limited thereto and may be used as a member for optical purposes other than the display body.
[0165] Examples of the display include a liquid crystal (LCD) display, a light emitting diode (LED) display, an organic electroluminescent (organic EL) display, and electronic paper. The display may be a touch panel.
[0166] Figure 2 FIG. 2 shows a specific structure of an optical laminate according to an embodiment of the present invention. Figure 2 As shown, the optical laminate 2A of this embodiment includes a first optical member 21 (one optical member), a second optical member 22 (another optical member), and a cured composite adhesive layer 11' located therebetween for bonding the first optical member 21 and the second optical member 22 to each other.
[0167] One of the first optical member 21 and the second optical member 22 may have a step on the surface on the side to be bonded by the cured composite adhesive layer 11 ′. Figure 2 In the illustrated embodiment, the first optical member 21 has a step due to the printed layer 23 on the surface on the composite pressure-sensitive adhesive layer 11 side.
[0168] The cured composite adhesive layer 11' in the display body 2A is a layer formed by curing the composite adhesive layer 11 of the adhesive sheet 1 with active energy rays. The cured composite adhesive layer 11' of the present embodiment is a laminate of a light diffusing adhesive layer 111 and a transparent adhesive layer 112, and the transparent adhesive layer 112 is located on the side in contact with the step based on the printed layer 23.
[0169] The first optical member 21 is preferably a protective panel composed of a laminate including a glass plate, a plastic plate, etc. In this case, the printed layer 23 is usually formed in a frame shape on the composite adhesive layer 11 side of the first optical member 21 .
[0170] The glass plate is not particularly limited, and examples thereof include chemically strengthened glass, alkali-free glass, quartz glass, soda-lime glass, barium-strontium-containing glass, aluminosilicate glass, lead glass, borosilicate glass, barium borosilicate glass, etc. The thickness of the glass plate is not particularly limited, but is usually 0.1 to 5 mm, preferably 0.2 to 2 mm.
[0171] The plastic plate is not particularly limited, and examples thereof include acrylic plates, polycarbonate plates, etc. The thickness of the plastic plate is not particularly limited, but is usually 0.2 to 5 mm, preferably 0.4 to 3 mm.
[0172] In addition, various functional layers (transparent conductive film, metal layer, silicon dioxide layer, hard coating layer, anti-glare layer, etc.) may be provided on one or both sides of the glass plate or plastic plate, and optical components may be laminated. In addition, the transparent conductive film and the metal layer may also be patterned.
[0173] The second optical component 22 is preferably an optical component to be attached to the first optical component 21, a display module (for example, a liquid crystal (LCD) module, a light emitting diode (LED) module, an organic electroluminescent (organic EL) module, etc.), an optical component that is part of a display module, or a stacked body including a display module.
[0174] As the above-mentioned optical member, for example, anti-scattering film, polarizing plate (polarizing film), polarizer, phase difference plate (phase difference film), viewing angle compensation film, brightness improvement film, contrast improvement film, liquid crystal polymer film, diffusion film, semi-transmissive reflection film, transparent conductive film, etc. can be listed. As the anti-scattering film, a hard coating film formed by forming a hard coating layer on one side of a substrate film can be exemplified.
[0175] The material constituting the printed layer 23 is not particularly limited, and known materials for printing can be used. The lower limit of the thickness of the printed layer 23, that is, the height of the step is preferably 3 μm or more, more preferably 5 μm or more, particularly preferably 7 μm or more, and most preferably 10 μm or more. By setting the lower limit to the above, it is possible to fully ensure that the electrical wiring is not visible from the observer's side. In addition, the upper limit is preferably 50 μm or less, more preferably 35 μm or less, particularly preferably 25 μm or less, and further preferably 20 μm or less. By setting the upper limit to the above, it is possible to prevent the composite adhesive layer 11' from deteriorating the step tracking of the printed layer 23 after curing, and to maintain the uniformity of light diffusion.
[0176] To produce the display 2A, as an example, one release sheet 12 a of the adhesive sheet 1 is peeled off, and the exposed transparent adhesive layer 112 of the adhesive sheet 1 is bonded to the surface of the first optical member 21 on the side where the printed layer 23 is present.
[0177] Then, another release sheet 12b is peeled off from the composite adhesive layer 11 of the adhesive sheet 1, and the light diffusing adhesive layer 111 exposed from the adhesive sheet 1 is bonded to the second optical member 22. In another example, the bonding order of the first optical member 21 and the second optical member 22 may be changed.
[0178] Next, the composite adhesive layer 11 is irradiated with active energy rays to form a cured composite adhesive layer 11'. The composite adhesive layer 11 is usually irradiated with energy rays through either the first optical member 21 or the second optical member 22, preferably through the first optical member 21 as a protective panel.
[0179] The active energy ray refers to an active energy ray having an energy quantum among electromagnetic waves or charged particle beams, and specific examples thereof include ultraviolet rays and electron beams, etc. Among the active energy rays, ultraviolet rays are preferred because they are easy to handle.
[0180] The ultraviolet irradiation can be performed using a high pressure mercury lamp, a fusion H lamp, a xenon lamp, etc., and the ultraviolet irradiation amount is preferably 50 to 1000 mW / cm 2 More preferably, it is 100 to 500 mW / cm 2 In addition, the light intensity is preferably 50 to 10000 mJ / cm 2 , more preferably 200 to 7000 mJ / cm 2 , particularly preferably 500 to 3000 mJ / cm 2 On the other hand, the electron beam irradiation can be performed using an electron beam accelerator or the like, and the irradiation amount of the electron beam is preferably about 10 to 1000 krad.
[0181] like Figure 3 As shown, a display body 2B of another embodiment is composed of a backlight source 30, a cured composite adhesive layer 11' laminated on the backlight source 30, and a display unit 40 laminated on the cured composite adhesive layer 11'. The backlight source 30 in the display body 2B belongs to the first optical component, and the display unit 40 belongs to the second optical component.
[0182] The backlight 30 includes one or more substrates 31 and a plurality of light emitters 32 provided on the substrate 31. The backlight 30 has projections and depressions due to the plurality of light emitters 32.
[0183] The cured composite adhesive layer 11' in the display body 2B is a layer formed by curing the composite adhesive layer 11 of the adhesive sheet 1 with active energy rays. The cured composite adhesive layer 11' of the present embodiment is a laminate of a light diffusion adhesive layer 111 and a transparent adhesive layer 112, and the transparent adhesive layer 112 is located on the side in contact with the concave and convex surface based on the luminous body 32. The plurality of luminous bodies 32 are sealed without any gap by the transparent adhesive layer 112. Thus, the luminous body 32 can be protected from the influence of moisture.
[0184] The substrate 31 is not particularly limited, and any substrate commonly used in backlight sources can be used. The substrate 31 is usually a printed circuit board (PCB substrate; Printed Circuit Board).
[0185] The substrate 31 may be formed in an integrated manner by mounting a plurality of light emitting bodies 32, or may be formed separately by mounting one light emitting body 32 on one substrate 31. When formed separately, each substrate 31 is usually fixed to a frame, a support, a housing, etc. In this embodiment, as shown in FIG. Figure 3 As shown, it is preferable that the substrate 31 is formed in an integrated manner so as to collectively mount a plurality of light-emitting bodies 32 .
[0186] A reflective layer may be formed on the surface of the substrate 31 on the composite adhesive layer 11 side, or a reflective member may be provided. This can effectively improve the brightness of the backlight 30. The reflective layer or the reflective member may be made of a known material.
[0187] Examples of the type of the light emitter 32 include light emitting diodes (LEDs), laser diodes (LDs), organic electroluminescent elements, inorganic electroluminescent elements, etc. Among them, LEDs are preferred, and mini LEDs or micro LEDs are particularly preferred, from the perspective of sealing properties provided by the composite adhesive layer 11' after curing.
[0188] The thickness of the luminous body 32 is preferably 10 μm or more, more preferably 30 μm or more, particularly preferably 50 μm or more, and further preferably 80 μm or more. In addition, the thickness of the luminous body 32 is preferably 300 μm or less, particularly preferably 150 μm or less, and further preferably 100 μm or less.
[0189] In addition, the width of the gap between adjacent light emitters 32 is preferably 0.01 mm or more, particularly preferably 0.1 mm or more, and further preferably 0.5 mm or more. In addition, the width of the gap is preferably 100 mm or less, more preferably 10 mm or less, particularly preferably 4 mm or less, and further preferably 2 mm or less.
[0190] The shape of the luminous body 32 is not particularly limited, and is usually a rectangular parallelepiped, a hemispherical shape, etc. The size of the luminous body 32 is also not particularly limited. From the perspective of the sealing performance of the luminous body, one side or diameter in a top view is preferably 0.01 to 100 mm, more preferably 0.1 to 10 mm, particularly preferably 0.2 to 5 mm, and further preferably 0.5 to 2 mm.
[0191] The light-diffusing adhesive layer 111 of the present embodiment diffuses the light emitted from the backlight 30 , and can effectively suppress the occurrence of uneven brightness.
[0192] The display unit 40 may be, for example, a liquid crystal panel, but is not limited thereto, and may be, for example, a part of a component of a liquid crystal panel, or an optical component (for example, a light diffusion plate or an ultraviolet absorption filter, etc.) used simultaneously to increase or enhance the function of the liquid crystal panel. The display unit 40 may be a known display unit.
[0193] In addition, a sealing material may be provided between the backlight source 30 and the cured composite adhesive layer 11'. In this case, the sealing material has many irregularities on the surface opposite to the backlight source 30, which can be absorbed by the transparent adhesive layer 112 of the cured composite adhesive layer 11'.
[0194] Furthermore, a desired optical member may be provided between the cured composite adhesive layer 11' and the display unit 40, or on the surface of the display unit 40 opposite to the cured composite adhesive layer 11'. Examples of the optical member include brightness enhancement films, contrast enhancement films, viewing angle compensation films, transparent conductive films, liquid crystal polymer films, semi-transmissive reflective films, and anti-scattering films.
[0195] To manufacture the display 2B of the present embodiment, for example, one release sheet 12 a of the adhesive sheet 1 is peeled off, and the exposed transparent adhesive layer 112 of the adhesive sheet 1 is bonded to the surface of the backlight 30 on the side where the light emitting body 32 is present.
[0196] Next, another release sheet 12b is peeled off from the composite adhesive layer 11 of the adhesive sheet 1, and the light diffusion adhesive layer 111 exposed by the adhesive sheet 1 is bonded to the display unit 40. Next, the composite adhesive layer 11 is irradiated with active energy rays to form a cured composite adhesive layer 11'. Alternatively, before bonding the display unit 40, the composite adhesive layer 11 is irradiated with active energy rays to form a cured composite adhesive layer 11', which is then bonded to the display unit 40 (peeling off the release sheet 12b). The irradiation conditions of the active energy rays are the same as those of the display body 2A.
[0197] As another example, the lamination order of the backlight source 30 and the display unit 40 may be changed.
[0198] The embodiments described above are described to facilitate understanding of the present invention, and are not described to limit the present invention. Therefore, each element disclosed in the above embodiments also covers all design changes or equivalents within the technical scope of the present invention.
[0199] For example, one or both of the release sheets 12 a and 12 b in the adhesive sheet 1 may be omitted, and a desired optical member may be laminated instead of the release sheets 12 a and / or 12 b.
[0200] Further, if Figure 4As shown in the adhesive sheet 1A shown, the composite adhesive layer 11 can also be formed by sequentially stacking a transparent adhesive layer 112, a light diffusion adhesive layer 111, and a transparent adhesive layer 112. The adhesive sheet 1A is effective when both the first optical member and the second optical member have a step difference (convex and concave) on the side of the composite adhesive layer 11. For example, when both the first optical member and the second optical member are liquid crystal panels, the adhesive sheet 1A is effective.
[0201] The embodiments described above are described to facilitate understanding of the present invention, and are not described to limit the present invention. Therefore, each element disclosed in the above embodiments also covers all design changes or equivalents within the technical scope of the present invention.
[0202] For example, any one of the release sheets 12 a and 12 b in the adhesive sheet 1 may be omitted.
[0203] Example
[0204] Hereinafter, the present invention will be described in more detail with reference to Examples, but the scope of the present invention is not limited to these Examples and the like.
[0205] [Manufacturing Example 1] (Preparation of a light-diffusing adhesive sheet)
[0206] 1. Preparation of (meth)acrylate polymers
[0207] A (meth)acrylate polymer (A) was prepared by copolymerizing 65 parts by mass of 2-ethylhexyl acrylate, 15 parts by mass of isobornyl acrylate, 5 parts by mass of N-acryloylmorpholine, and 15 parts by mass of 2-hydroxyethyl acrylate by solution polymerization. The molecular weight of the (meth)acrylate polymer (A) was measured by the following method, and the weight average molecular weight (Mw) was 500,000.
[0208] 2. Preparation of adhesive composition
[0209] 100 parts by mass of the (meth)acrylate polymer (A) obtained in the above step 1 (solid content conversion value; the same applies hereinafter), 0.20 parts by mass of trimethylolpropane-modified toluene diisocyanate (manufactured by TOYO KAGAKU, INC., product name "BHS8515") as a crosslinking agent (B), 5.2 parts by mass of ε-caprolactone-modified tris-(2-acryloyloxyethyl)isocyanurate (manufactured by SHIIN-NAKAMURA CHEMICAL CO. LTD., product name "NK Ester A-9300-1CL") as an active energy ray-curable component (C), and fine particles composed of silicone resin (a silicon-containing compound having a structure intermediate between inorganic and organic) (Momentive Performance Materials Japan Inc., product name "Tospearl 145", average particle size: 4.5 μm), 5.0 parts by mass of 2,4,6-trimethylbenzoyl-diphenyl-phosphine oxide as a photopolymerization initiator (E), and 0.2 parts by mass of 3-glycidyloxypropyltrimethoxysilane as a silane coupling agent were mixed, stirred thoroughly, and diluted with methyl ethyl ketone to obtain a coating solution of the adhesive composition.
[0210] Here, each compounding ratio (solid content conversion value) of the adhesive composition when the (meth)acrylate polymer (A) is set to 100 parts by mass (solid content conversion value) is shown in Table 1. In addition, the details of the abbreviations and the like described in Table 1 are as follows.
[0211] [(Meth)acrylate polymer (A)]
[0212] 2EHA: 2-Ethylhexyl acrylate
[0213] IBXA: Isobornyl acrylate
[0214] ACMO: N-acryloylmorpholine
[0215] HEA: 2-Hydroxyethyl Acrylate
[0216] BA: n-butyl acrylate
[0217] AA: Acrylic acid
[0218] [Crosslinking agent (B)]
[0219] TDI: Trimethylolpropane-modified toluene diisocyanate (manufactured by TOYO KAGAKU, INC., product name "BHS8515")
[0220] XDI type: trimethylolpropane-modified xylylene diisocyanate (manufactured by Soken Chemical & Engineering Co., Ltd., product name "TD-75")
[0221] Epoxy: 1,3-bis(N,N-diglycidylaminomethyl)cyclohexane (manufactured by MITSUBISHI GAS CHEMICAL COMPANY, INC., product name "TETRAD-C")
[0222] [Light-diffusing particles (D)]
[0223] D1: microparticles composed of silicone resin (a silicon-containing compound having a structure intermediate between inorganic and organic) with an average particle diameter of 4.5 μm (produced by Momentive Performance Materials Japan Inc., product name "Tospearl 145", refractive index: 1.43)
[0224] D2: Microparticles composed of silicone resin (a silicon-containing compound having a structure intermediate between inorganic and organic) with an average particle diameter of 2.0 μm (produced by Momentive Performance Materials Japan Inc., product name "Tospearl 120", refractive index: 1.43)
[0225] D3: spherical polymethyl methacrylate-polystyrene copolymer microparticles having an average particle diameter of 4.0 μm (manufactured by Sekisui Kasei Co., Ltd., product name “XX-30LA”, refractive index: 1.56)
[0226] 3. Fabrication of light-diffusing adhesive sheets
[0227] Using a blade coater, the coating solution of the adhesive composition obtained in the above step 2 is applied to the release-treated surface of a heavy-release release sheet (manufactured by Lintec Corporation, product name "SP-PET752150") having one side of a polyethylene terephthalate film subjected to release treatment using a silicone release agent, and then heat-treated at 90°C for 1 minute to form a coating layer (thickness: 50 μm).
[0228] Next, the coating layer on the heavy-peelable release sheet obtained above is laminated with a light-peelable release sheet (manufactured by Lintec Corporation, product name "SP-PET381031") obtained by subjecting one side of a polyethylene terephthalate film to a release treatment using a silicone release agent so that the release-treated surface of the light-peelable release sheet is in contact with the coating layer, thereby producing a light-diffusing adhesive sheet having a structure of heavy-peelable release sheet / light-diffusing adhesive layer (a) coating layer (thickness: 50 μm) / light-peelable release sheet.
[0229] The thickness of the light diffusing adhesive layer is a value measured using a constant pressure thickness meter (manufactured by TECLOCK CO., LTD., product name “PG-02”) in accordance with JIS K7130 (the same shall apply hereinafter).
[0230] [Manufacturing Examples 2 to 7, 9 to 10] (Manufacturing of Light Diffusing Adhesive Sheets)
[0231] Except that the types and proportions of the monomers constituting the (meth)acrylate polymer (A), the weight average molecular weight (Mw) of the (meth)acrylate polymer (A), the blending amount of the crosslinking agent (B), the blending amount of the active energy ray-curable component (C), the type and blending amount of the light-diffusing fine particles (D), the blending amount of the photopolymerization initiator (E), and the blending amount of the silane coupling agent are changed to those shown in Table 1, a light-diffusing adhesive sheet having a light-diffusing adhesive layer (b) (Manufacturing Example 2), a light-diffusing adhesive layer (c) (Manufacturing Example 3), a light-diffusing adhesive layer (d) (Manufacturing Example 4), a light-diffusing adhesive layer (e) (Manufacturing Example 5), a light-diffusing adhesive layer (f) (Manufacturing Example 6), a light-diffusing adhesive layer (g) (Manufacturing Example 7), a light-diffusing adhesive layer (i) (Manufacturing Example 9), and a light-diffusing adhesive layer (j) (Manufacturing Example 10) is prepared in the same manner as in Manufacturing Example 1. The light diffusing adhesive sheet having the light diffusing adhesive layer (j) (Production Example 10) was previously irradiated with active energy rays (ultraviolet rays) through a light release type release sheet under the same conditions as in Test Example 1 described below to cure the light diffusing adhesive layer.
[0232] [Manufacturing Example 8] (Preparation of a transparent adhesive sheet)
[0233] A transparent adhesive sheet having a transparent adhesive layer (h) (Manufacture Example 8) was prepared in the same manner as in Manufacture Example 1, except that the type and ratio of each monomer constituting the (meth)acrylate polymer (A), the weight average molecular weight (Mw) of the (meth)acrylate polymer (A), the blending amount of the crosslinking agent (B), the blending amount of the active energy ray curable component (C), the blending amount of the light diffusing fine particles (D) (not blended), the blending amount of the photopolymerization initiator (E), and the blending amount of the silane coupling agent were changed to those shown in Table 1. In addition, the transparent adhesive sheet having a transparent adhesive layer (h) used in Example 9 was irradiated with active energy rays (ultraviolet rays) in advance through a light release type release sheet under the same conditions as in Test Example 1 described later, thereby curing the transparent adhesive layer.
[0234] The weight average molecular weight (Mw) is a polystyrene-equivalent weight average molecular weight measured under the following conditions using gel permeation chromatography (GPC) (GPC measurement).
[0235] <Measurement conditions>
[0236] ·GPC measuring apparatus: HLC-8020 manufactured by TOSOH CORPORATION
[0237] ·GPC columns (passed in the following order): manufactured by TOSOH CORPORATION
[0238] TSK guard column HXL-H
[0239] TSK gel GMHXL (×2)
[0240] TSK gel G2000HXL
[0241] ·Test solvent: tetrahydrofuran
[0242] ·Measurement temperature: 40℃
[0243] [Example 1]
[0244] The light-peelable release sheet is peeled off from the light-diffusing adhesive sheet prepared in Manufacturing Example 1 to expose the coating layer of the light-diffusing adhesive layer (a). In addition, the light-peelable release sheet is peeled off from the transparent adhesive sheet prepared in Manufacturing Example 8 to expose the coating layer of the transparent adhesive layer (g). The coating layer of the transparent adhesive layer (g) is stacked on the coating layer of the light-diffusing adhesive layer (a), and then aged for 7 days under the conditions of 23°C and 50% RH. In this way, an adhesive sheet consisting of a heavy-peelable release sheet / light-diffusing adhesive layer (a) (50 μm) / transparent adhesive layer (g) (50 μm) / heavy-peelable release sheet is manufactured (light-diffusing adhesive layer + transparent adhesive layer = composite adhesive layer).
[0245] [Examples 2 to 9, Comparative Examples 1 to 3]
[0246] The adhesive sheet was manufactured in the same manner as in Example 1 except that the types of the light-diffusing adhesive layer and the transparent adhesive layer were changed to those shown in Table 2. In addition, in Table 2, for convenience, the light-diffusing adhesive layer in the column of the light-diffusing adhesive layer in Comparative Example 1 is also described as the transparent adhesive layer, and the light-diffusing adhesive layer in the column of the transparent adhesive layer in Comparative Examples 2 and 3 is also described as the light-diffusing adhesive layer.
[0247] [Test Example 1] (Measurement of gel fraction)
[0248] The adhesive sheets (after aging) prepared in each manufacturing example and the adhesive sheets obtained in the examples and comparative examples were cut into a size of 80 mm × 80 mm, and the adhesive layer was wrapped in a polyester net (mesh size 200), and its mass was weighed with a precision balance, and the mass of the net alone was subtracted to calculate the mass of the adhesive itself. The mass at this time was recorded as M1.
[0249] Next, at room temperature (23°C), immerse the adhesive wrapped in the polyester net in ethyl acetate for 24 hours. Then take out the adhesive, air-dry it for 24 hours at a temperature of 23°C and a relative humidity of 50%, and further dry it in an oven at 80°C for 12 hours. After drying, weigh its mass with a precision balance, subtract the mass of the net alone, and calculate the mass of the adhesive itself. The mass at this time is recorded as M2. The gel fraction (%) is expressed as (M2 / M1)×100. From this, the gel fraction of the adhesive (before UV) is derived. The results are shown in Table 2.
[0250] On the other hand, the adhesive layer of the adhesive sheet (after aging) prepared in each manufacturing example and the adhesive sheet obtained in the embodiment and the comparative example (except manufacturing example 10 and comparative example 3) was irradiated with active energy rays (ultraviolet rays; UV) through a light peeling type release sheet under the following conditions to cure the adhesive layer to prepare a cured adhesive layer. For the adhesive of the cured adhesive layer, the gel fraction (after UV) was derived in the same manner as above. The results are shown in Table 2.
[0251] <Active energy ray irradiation conditions>
[0252] Use high pressure mercury lamp
[0253] Illuminance 200mW / cm 2 , light intensity 1000mJ / cm 2
[0254] · UV illuminance-light meter used was "UVPF-A1" manufactured by EYE GRAPHICS Co., Ltd.
[0255] [Test Example 2] (Measurement of storage modulus)
[0256] The release sheet was peeled off from the adhesive sheet (after aging) prepared in each manufacturing example and the adhesive sheet obtained in the embodiment and the comparative example, and a plurality of adhesive layers were stacked in such a manner that the thickness became 800 μm. A cylinder with a diameter of 8 mm (height of 800 μm) was punched out from the laminate of the obtained adhesive layer and used as a sample.
[0257] The storage modulus (GD1, GT1, G1) (before UV; MPa) at 23° C. was measured for the samples using a viscoelasticity measuring apparatus (manufactured by Physica Corporation, product name “MCR300”) by a torsional shear method under the following conditions in accordance with JIS K7244-6. The results are shown in Table 2.
[0258] Measuring frequency: 1Hz
[0259] Measurement temperature: 23°C
[0260] In addition, the same samples as those described above (except for Preparation Example 10 and Comparative Example 3) were irradiated with active energy rays (ultraviolet rays; UV) under the same conditions as in Test Example 1 to cure the adhesive, thereby obtaining samples irradiated with active energy rays. The storage modulus (GD2, GT2, G2) (after UV; MPa) of the obtained samples irradiated with active energy rays at 23°C was measured in the same manner as the samples before irradiation with active energy rays. The results are shown in Table 2.
[0261] In addition, the storage modulus change rate (ΔGD, ΔGT, ΔG') was calculated as the ratio (GD2 / GD1, GT2 / GT1, G2 / G1) of the storage modulus (GD2, GT2, G2) after irradiation with active energy rays to the storage modulus (GD1, GT1, G1) before irradiation with active energy rays. The results are shown in Table 2.
[0262] [Test Example 3] (Measurement of Haze Value)
[0263] The composite adhesive layer of the adhesive sheet manufactured in the embodiment and the comparative example was bonded to glass, which was used as a sample for measurement. Based on the background measurement using glass, the haze value (%) of the above-mentioned sample for measurement was measured using a haze meter (manufactured by Nippon Denshoku Industries Co., Ltd., product name "SH-7000") in accordance with JIS K7136:2000. The results are shown in Table 2.
[0264] [Test Example 4] (Measurement of total light transmittance)
[0265] The composite adhesive layer of the adhesive sheet manufactured in the embodiment and the comparative example was bonded to glass and used as a sample for measurement. Based on the background measurement using glass, the total light transmittance (%) of the above-mentioned sample for measurement was measured using a haze meter (manufactured by Nippon Denshoku Industries Co., Ltd., product name "SH-7000") in accordance with K7361-1:1997. The results are shown in Table 2.
[0266] [Test Example 5] (Measurement of Adhesion Strength)
[0267] The heavy peelable release sheet on the light diffusing adhesive layer side was peeled off from the adhesive sheet obtained in the embodiment and the comparative example, and the exposed light diffusing adhesive layer was attached to the easy adhesive layer of a polyethylene terephthalate (PET) film (manufactured by TOYOBO Co., Ltd., product name "PET A4300", thickness: 100 μm) having an easy adhesive layer to obtain a laminate of heavy peelable release sheet / composite adhesive layer / PET film. The obtained laminate was cut into 25 mm wide and 100 mm long.
[0268] Under the environment of 23 ℃ and 50% RH, the heavy peeling type peeling sheet on the side of the transparent adhesive layer is peeled off from the above-mentioned laminate, and the exposed transparent adhesive layer is attached to a soda-lime glass (manufactured by Nippon Sheet Glass Co., Ltd), and then the autoclave manufactured by Kurihara Manufacturing Co. is used to pressurize for 20 minutes at 0.5MPa and 50 ℃. Then, it is placed under the conditions of 23 ℃ and 50% RH for 24 hours and used as a sample. In addition, using a tensile testing machine (manufactured by ORIENTEC CORPORATION, product name "TENSILON"), the adhesion (transparent adhesive layer-UV front; N / 25mm) is measured under the conditions of a peeling speed of 300mm / minute and a peeling angle of 180 degrees. Regarding the conditions not described here, the measurement is carried out in accordance with JIS Z0237:2009.
[0269] Next, the sample was irradiated with active energy rays through the PET film under the same conditions as in Test Example 1 to cure the composite adhesive layer to prepare a cured composite adhesive layer. The adhesive force of the cured composite adhesive layer was measured in the same manner as above (transparent adhesive layer-after UV; N / 25 mm). The results are shown in Table 2.
[0270] In addition, the adhesive force before UV on the light-diffusing adhesive layer side (light-diffusing adhesive layer-before UV; N / 25 mm) and the adhesive force after UV on the light-diffusing adhesive layer side (light-diffusing adhesive layer-after UV; N / 25 mm) were measured in the same manner as above. The results are shown in Table 2.
[0271] [Test Example 5] (Evaluation of step followability)
[0272] On the surface of a glass plate (manufactured by NSG Precision Cells, Inc., product name "corning glass eagle XG", 90 mm in length × 50 mm in width × 0.5 mm in thickness), an ultraviolet curing ink (manufactured by Teikoku Printing Inks Mfg. Co., Ltd., product name "POS-911 ink") was screen-printed in a frame shape (outer shape: 90 mm in length × 50 mm in width, 5 mm in width). Then, ultraviolet rays (80 W / cm 2 , 2 metal halide lamps, lamp height 15 cm, belt speed 10-15 m / min), the printed ultraviolet curing ink is cured to manufacture a glass plate with a step difference based on printing (the height of the step difference: 5μm, 10μm, 15μm and 20μm).
[0273] The heavy peeling peeling sheet on the light-diffusing adhesive layer side is peeled off from the adhesive sheet obtained in the embodiment and the comparative example, and the exposed light-diffusing adhesive layer is bonded to a soda-lime glass plate (manufactured by Nippon Sheet Glass Co., Ltd, thickness: 0.7 mm). Next, the heavy peeling peeling sheet on the transparent adhesive layer side is peeled off to expose the transparent adhesive layer. Then, using a laminator (manufactured by FUJIPLA Inc., product name "LPD3214"), the above-mentioned laminate is laminated on each glass plate with a step difference in such a way that the composite adhesive layer covers the entire frame-shaped printing surface. Then, a heat treatment is performed at 50°C and 0.5MPa for 30 minutes, and the laminate is placed at normal pressure, 23°C, and 50%RH for 24 hours.
[0274] Next, the composite adhesive layer was cured by irradiating active energy rays through the soda-lime glass plate under the same conditions as in Test Example 1 to prepare a cured composite adhesive layer (except for Comparative Example 3). Next. Store under 85°C, 85% RH wet and hot conditions for 72 hours (durability test). Then, the step tracking performance was evaluated based on the following standards. The results are shown in Table 2.
[0275] ◎: Follows all height differences without bubbles, floating or peeling.
[0276] ○: The film followed all the height differences before the durability test, but bubbles, floating, and peeling occurred at the differences with a height of 15 μm or more after the durability test.
[0277] ×: Bubbles or floating occurred before the durability test.
[0278] [Test Example 6] (Evaluation of anti-foaming properties)
[0279] The heavy-peel peeling sheet on the transparent adhesive layer side is peeled off from the adhesive sheet obtained in the embodiment and the comparative example, and the exposed transparent adhesive layer is adhered to the PC board side of a plastic plate (manufactured by MITSUBISHI GAS CHEMICAL COMPANY, INC., product name "yupilon sheet MR58U", thickness: 0.7 mm, containing ultraviolet absorber) having a PMMA layer laminated on a PC board to obtain a plastic plate with a composite adhesive layer.
[0280] The heavy-peelable release sheet on the light-diffusing adhesive layer side of the plastic plate with the composite adhesive layer obtained above was peeled off, and the plastic plate was attached to a 70 mm×150 mm soda-lime glass plate (manufactured by Nippon Sheet Glass Co., Ltd., thickness: 0.7 mm) via the exposed light-diffusing adhesive layer. Then, an autoclave treatment was performed at 50° C. and 0.5 MPa for 30 minutes, and the plate was left at normal pressure, 23° C., and 50% RH for 24 hours.
[0281] Next, the composite adhesive layer was irradiated with active energy rays through a soda-lime glass plate under the same conditions as in Test Example 1 to cure the composite adhesive layer to prepare a cured composite adhesive layer (except for Comparative Example 3). In this way, a laminate (70 mm×150 mm) in which a plastic plate and a glass plate were bonded together using a cured composite adhesive layer was obtained.
[0282] The laminate was stored at 85°C and 85%RH for 72 hours. The state of the interface between the cured composite adhesive layer and the adherend (plastic plate, glass plate) was visually confirmed, and the anti-foaming property was evaluated according to the following criteria. The results are shown in Table 2.
[0283] ◎···No bubbles, floating or peeling.
[0284] ○···Micro bubbles were generated.
[0285] ×···The entire system has bubbles, floating, or peeling.
[0286] [Test Example 7] (Evaluation of Brightness Unevenness Suppression Property)
[0287] As a surface light source, a liquid crystal display device of a tablet terminal (manufactured by Apple Inc., product name "iPad (registered trademark)", resolution: 264ppi) was prepared. The surface of the liquid crystal display device was covered with a stainless steel mesh to obtain a simulated point light source. In addition, the conditions of the above-mentioned liquid crystal display device and the details of the stainless steel mesh are as follows.
[0288] <Liquid crystal display device>
[0289] Display color: White
[0290] Brightness setting: Maximum
[0291] Pixel count: 980×980
[0292] <Stainless steel mesh>
[0293] ·Stainless steel type: SUS316
[0294] ·Weaving method: plain weave
[0295] Wire diameter: 50μm
[0296] Pore diameter: 204 μm
[0297] Opening rate: 64.5%
[0298] ·Mesh: 100( / 25.4mm)
[0299] On the other hand, the light diffusing adhesive layer-side surface of the adhesive sheets obtained in Examples and Comparative Examples was bonded to a soda lime glass plate (manufactured by Nippon Sheet Glass Co., Ltd., thickness: 0.7 mm), and the obtained laminate was used as a sample.
[0300] The sample was placed on the simulated point light source in such a way that the transparent adhesive layer side of the sample was in contact with the simulated point light source, and the sensory evaluation was performed by visually confirming whether the metal wire was visible from a position 30 cm directly above the sample. Based on the result, the brightness unevenness suppression was evaluated according to the following criteria. The results are shown in Table 2.
[0301] ◎···The metal wire is hidden and the brightness is evenly distributed.
[0302] ○···When staring closely, metal threads can be confirmed, but the brightness distribution is roughly uniform.
[0303] ×···Metallic wires can be clearly seen, and the brightness distribution is uneven.
[0304]
[0305]
[0306] As can be seen from Table 2, the adhesive sheets produced in Examples have excellent step-following properties and are also excellent in suppressing uneven brightness. In addition, the adhesive sheets produced in Examples 1 to 8 are also excellent in anti-foaming properties.
[0307] Industrial Applicability
[0308] The pressure-sensitive adhesive sheet and optical layered body of the present invention are suitably used for members or devices requiring uniform light diffusion and durability, and are particularly suitably used for liquid crystal displays and the like.
Claims
1. An adhesive sheet, characterized in that: The composite adhesive layer comprises a light-diffusing adhesive layer containing light-diffusing particles and a transparent adhesive layer containing no light-diffusing particles. The light-diffusing adhesive layer and the transparent adhesive layer are both composed of an active energy ray-curable adhesive.
2. The adhesive sheet according to claim 1, characterized in that The haze value of the composite adhesive layer is 40% to 99%.
3. The adhesive sheet according to claim 1, characterized in that The storage modulus G1 of the composite adhesive layer at 23° C. is 0.001 MPa or more and 0.2 MPa or less.
4. The adhesive sheet according to claim 1, characterized in that The storage modulus G2 of the composite adhesive layer at 23° C. after irradiation with active energy rays is 0.08 MPa or more and 10 MPa or less.
5. The adhesive sheet according to claim 1, characterized in that The storage modulus change rate ΔG′, which is a ratio of the storage modulus G2 of the composite adhesive layer at 23° C. to the storage modulus G1 of the composite adhesive layer at 23° C. after irradiation with active energy rays, is 1.1 or more and 100 or less.
6. The adhesive sheet according to claim 1, wherein The adhesive strength of the transparent adhesive layer side of the adhesive sheet to the soda-lime glass is 20 N / 25 mm or more and 80 N / 25 mm or less.
7. The adhesive sheet according to claim 1, wherein The adhesive strength of the transparent adhesive layer side of the adhesive sheet to the soda-lime glass after irradiation with active energy rays is 20 N / 25 mm or more and 80 N / 25 mm or less.
8. The adhesive sheet according to claim 1, wherein The light diffusing adhesive layer side of the adhesive sheet has an adhesive force to the soda-lime glass of not less than 1 N / 25 mm and not more than 60 N / 25 mm.
9. The adhesive sheet according to claim 1, wherein The light diffusing adhesive layer side of the adhesive sheet has an adhesive strength to soda-lime glass of 10 N / 25 mm or more and 60 N / 25 mm or less after irradiation with active energy rays.
10. The adhesive sheet according to claim 1, wherein The composite adhesive layer has a thickness of 20 μm to 1000 μm.
11. The adhesive sheet according to claim 1, wherein The light diffusing adhesive layer has a thickness of 10 μm to 500 μm.
12. The adhesive sheet according to claim 1, wherein The transparent adhesive layer has a thickness of 10 μm to 500 μm.
13. The adhesive sheet according to claim 1, wherein The composite adhesive layer is provided with two release sheets, and the composite adhesive layer is sandwiched by the release sheets in a manner of being in contact with release surfaces of the two release sheets.
14. An optical laminate comprising an optical member, another optical member, and a cured composite adhesive layer for bonding the one optical member and the other optical member to each other, characterized in that: The cured composite adhesive layer is a layer formed by curing the composite adhesive layer of the adhesive sheet according to any one of claims 1 to 13 with active energy rays.
15. The optical layered body according to claim 14, characterized in that: At least one of the one optical member and the other optical member has irregularities on a surface on a side to be bonded by the cured composite adhesive layer, and the transparent adhesive layer of the cured composite adhesive layer is in contact with the irregularities.
